Beyond the dung heap: the reliability of spores of the ascomycete fungal genus Sporormiella (incl. Preussia) as a proxy indicator of dung and grazing animals - David L. Hawksworth; Patricia E.J. Wiltshire; K. Anupama; M.B. Govinda Rajulu; N. Thirunavukkarasu; S. Prasad; Kevin J. Edwards; T.S. Suryanarayanan (Review of Palaeobotany and Palynology, 2026)

Exploring Holocene non-pollen palynomorph data from the Isle of Mull, Scottish Inner Hebrides: Ecological harmonisation and taphonomic complexity - Kevin J. Edwards; James B. Innes; J. Edward Schofield; Heather Sugden; Jeff J. Blackford (Review of Palaeobotany and Palynology, 2026)

Investigation of paleoseismic deposits in Jackson Lake, WY associated with the far afield 1959 Mw 7.2 Hebgen Lake earthquake (MT, USA) - Samuel J. Whitehead; Kevin M. Yeager; Michael M. McGlue; J. Ryan Thigpen; Kimberly J. Schindler; Edward W. Woolery (Sedimentary Geology, 2026)

Influence of climate warming on peatland net mercury gas fluxes: Results from the SPRUCE experiment - Isabella M. Garrioch; Kevin Behrens; Edward A. Nater; Randall K. Kolka (Journal of Environmental Management, 2026)

Palynological data from Loch an t’Suidhe, Isle of Mull, Scotland - Kevin J. Edwards; Heather Sugden; James B. Innes; Jeff Blackford; J. Edward Schofield (Palynology, 2026)

Mixed Support for Pleistocene Sea‐Level Fluctuations in Promoting the Diversification of Anole Lizards in the Northern Lesser Antilles - Ayanna J. Browne; Edward A. Myers; S. Blair Hedges; Kevin de Queiroz; Robert Powell; Lauren A. Esposito; Rayna C. Bell; Michael L. Yuan (Molecular Ecology, 2026)
In the Pleistocene, climatic changes resulted in cycles of sea‐level fluctuation that periodically fragmented islands into aggregate island complexes. These temporary saltwater barriers between islands within an island bank had the potential to decrease migration between populations on separate islands, resulting in increased genetic divergence and potentially speciation. In the Lesser Antilles, Anolis lizards (anoles) are distributed across island banks that vary in distance and water depth between islands, making them excellent candidates for studying how different barriers shape patterns of genetic diversity. Here, we focused on anoles found across the St. Kitts Bank ( A. bimaculatus , A . schwartzi ), Anguilla Bank ( A. gingivinus ), and Barbuda Bank ( A. leachii , A. wattsi ) to test the hypothesis that populations separated by narrower and shallower marine barriers are more genetically similar to one another than populations on more distant islands or those separated by deeper water. Using a combination of mitochondrial and nuclear genomic DNA, we found a spectrum of population genetic structure ranging from weak but detectable structure ( A. gingivinus , Anguilla Bank and A. leachii , Barbuda Bank) to pronounced ( A. bimaculatus and A. schwartzi , St. Kitts Bank) and even species divergence ( A. wattsi complex, Barbuda Bank). The extent of genetic divergence, however, did not consistently correspond to island bathymetry. Our demographic analyses for each currently recognized species supported a model of divergence with gene flow, consistent with a history of intermittent migration between present‐day islands. Collectively, these results support a partial role for sea‐level fluctuations in the Pleistocene structuring current patterns of genetic diversity in Lesser Antillean anoles.

Response to Letter to the Editor: “Recurrence and mortality after Pseudomonas aeruginosa bloodstream infection” - Felicity Edwards; Kevin B. Laupland (European Journal of Clinical Microbiology & Infectious Diseases, 2026)

The Queensland Bloodstream Infections (QBSI) study: rationale, protocol development and future directions - Kevin B. Laupland; Felicity Edwards; Patrick N. A. Harris; Adam Irwin; Burcu Isler; Holly Hamilton; Sonali Coulter; Adam G. Stewart (Infectious Diseases, 2026)

Impacts of sub-daily rapid temperature drops on winter outdoor thermal comfort under climate change: A case study in Hong Kong - Lingye Yao; Kai Gao; Kevin Lau; Zhixin Liu; Chao Ren; Jimmy Chi Hung Fung; Edward Ng (Urban Climate, 2026)

Beyond summer cooling: Evaluating winter thermal performance of urban trees in subtropical coastal region - Lingye Yao; Kevin Lau; Xiang Zhang; Zhixin Liu; Genyu Xu; Kai Gao; Mohammad A. Rahman; Edward Ng (Building and Environment, 2026)

Spatial optimization of the sustainable aviation fuel supply chains from forest residues via fast pyrolysis/hydrotreatment considering feedstock ash content variability - Pengzhen Li; T. Edward Yu; Nicole Labbé; Nourredine Abdoulmoumine; Manuel Garcia-Perez; Kevin P. Hoyt; Burton C. English (Biomass and Bioenergy, 2026)

Interpretable deep learning reveals spatiotemporal MRI features of brain aging that align with neurodegeneration - Nikhil N. Chaudhari; Owen M. Vega; Phoebe Imms; Jaron M. Kawamura; Nahian F. Chowdhury; Tamara Jafar; Andrei Irimia; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2026)
Cortical thinning and atrophy are hallmarks of brain aging that have been characterized using magnetic resonance imaging (MRI). Brain aging involves many neuroanatomic features whose effects on brain structure remain unexplored. To address this challenge, we trained interpretable deep neural networks (DNNs) to estimate brain age (BA) from T 1 -weighted ( T 1 w) MRI. By identifying MRI features unapparent to humans, DNNs can find aging-related structural alterations above and beyond cortical thickness and atrophy. Using a novel approach to DNN interpretability, we mapped brain aging progression in 25,539 cognitively normal UK Biobank adults aged 45–83 years. Cortical aging is found to involve anatomic features becoming prominent during the 50s within frontolateral, mesolimbic, cuneal, and occipitotemporal regions. From these foci, aging-related features propagate to adjacent areas at rates peaking in the 60s. Cortical thinning and atrophy do not trend closely with neurodegeneration, but important DNN-identifiable anatomic features have spatiotemporal dynamics that match those of amyloid or tau. Our results challenge the assumption that MRI cannot map anatomic features trending with neurodegeneration. Interpretable DNNs can empower MRI to quantify anatomic aging as a process of spatial feature expansion from focal regions into nearby structures in the sequence of neurodegenerative pathology. Traditional morphometrics explain only ∼1% of variance in DNN-identifiable features, which clarifies why the former are insensitive to anatomic changes involving neurodegeneration. Our results conceptualize brain aging in the context of spatial and temporal parallels between anatomic senescence and neuropathology. These findings may help to map cognitively normal adults’ neurodegenerative anatomy even without PET measurements. Graphical Abstract

Designing for mild winters: evidence-based thermal comfort benchmarks from urban parks in a sub-tropical city - Kevin Lau; Lingye Yao; Edward Ng (International Journal of Biometeorology, 2026)
Outdoor thermal comfort in the cool season remains under-specified for humid subtropical cities. We conducted a winter field study across four urban parks in Hong Kong, collecting 611 paired questionnaire-microclimate records (December-March). On-site measurements (air temperature, globe temperature, humidity, wind) were linked at 60-s resolution to Cantonese surveys of thermal sensation. Neutral temperature was estimated with ordinary least squares and confirmed with proportional-odds models; 2,000-fold bootstrap confidence intervals and 0.5 °C binned regressions quantified uncertainty and sensitivity. Whole-sample neutral points were Air Temperature (T a ) 20.6 °C (95% CI 19.7–21.6 °C), Physiological Equivalent Temperature (PET) 23.7 °C (22.2–25.8 °C), and Universal Thermal Climate Index (UTCI) 20.7 °C (19.3–22.5 °C). T a was the strongest single predictor of mean thermal sensation in binned fits (R² = 0.62), followed by UTCI (R² = 0.54) and PET (R²= 0.22). Females showed slightly steeper vote-temperature slopes but similar neutralities to males. Age had a clear effect: neutral UTCI rose from 18.6 °C (< 60 years) to 23.1 °C (> 75 years), with flatter slopes in older cohorts. Park type also mattered. Neutral PET and UTCI were about 2 °C warmer in larger, greener district parks than in compact street parks, consistent with higher sky-view and lower turbulence. Robustness checks (ordinal-logit, trimmed bins, meteorological filtering) shifted whole-sample neutralities by ≤ 0.4 °C. We propose UTCI 20–22 °C as a practical winter design target for subtropical parks, complemented by 2–3 °C warmer micro-niches for older users through solar access and wind shelter. These calibrated benchmarks support climate-responsive park design that sustains outdoor use through mild winters in ageing, high-density cities.

Recurrence and mortality after Pseudomonas aeruginosa bloodstream infection: a population-based cohort study - Felicity Edwards; Michael Waller; Kevin B. Laupland (European Journal of Clinical Microbiology & Infectious Diseases, 2026)

The collective application of shorebird tracking data to conservation - Autumn‐Lynn Harrison; Candace Stenzel; Alexandra Anderson; Jessica Howell; Richard B. Lanctot; Marley Aikens; Joaquín Aldabe; Liam A. Berigan; Joël Bêty; Erik Blomberg; Juliana Bosi de Almeida; Andy J. Boyce; et al. (Conservation Biology, 2026)
Addressing urgent conservation issues, such as the drastic declines of North American migratory birds, requires creative, evidence‐based, efficient, and collaborative approaches. The abundance of over 50% of monitored North American shorebird populations has declined by over 50% since 1980. To address these declines, we developed a partnership of scientists and practitioners called the Shorebird Science and Conservation Collective (hereafter the collective ). The collective was founded to translate the combined findings of shorebird tracking data into on‐the‐ground conservation action. With advice from an advisory group, the collective acts as an intermediary whereby dedicated staff collate and analyze data contributions from scientists to support knowledge requests from conservation practitioners. In its first three years, data contributions from 75 organizations include over 7.1 million shorebird observations forming movement paths of 3420 individuals representing 36 species tracked across the Americas and have informed 18 conservation projects spanning education, land and species management, land conservation, and policy requests. Others engaged in translational science from big data could consider similar knowledge‐sharing models that prioritize usable data products, foster collaborative engagement between science experts and practitioners, build focused communities around topics or taxonomic groups, and employ a proof‐of‐concept phase to develop scalable solutions while making progress toward long‐term funding to sustain impact. As the volume of scientific data continues to grow, intermediaries, such as the collective, can be vital liaisons to rapidly integrate and interpret research to support conservation action. Dedicated to the memory of Shiloh Schulte and his conservation achievements for shorebirds.

Sex and APOE genotype specific brain regional vulnerability to Alzheimer's Disease - Qi Zeng; Minghui Wang; Erming Wang; Xianxiao Zhou; Peng Xu; Vahram Haroutunian; Dongming Cai; Bin Zhang; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2026)
Alzheimer’s disease (AD) disproportionately affects women and carriers of the apolipoprotein E ε4 allele (APOE4), yet little is known about how sex and APOE interact to influence white matter (WM) integrity during disease progression. We integrated diffusion MRI and matched blood transcriptomic data to investigate these interactions and their underlying biological mechanisms. WM microstructure was quantified using diffusion tensor imaging (DTI) and neurite orientation dispersion and density imaging (NODDI), and regional vulnerability was assessed with a composite vulnerability score (CVS) derived from associations between diffusion features and AD severity across clinical traits in each of the four sex-APOE groups (female or male, with or without APOE4). Brain parcellation with the Eve atlas revealed regions consistently affected across sex-APOE groups (e.g., parahippocampal and superior temporal gyri) and regions specific to individual groups (e.g., the cingulum in females with APOE4 and the middle frontal gyrus in males without APOE4). Gene co-expression network analysis of the matched blood expression data identified gene subnetworks linked to group-specific regional vulnerability, including a muscle tissue morphogenesis module regulated by NEURL1B and HIST1H2BN associated with middle frontal gyrus vulnerability. These findings demonstrate that sex and APOE genotype jointly shape region-specific WM vulnerability and its molecular signatures in AD. Understanding these interactions provides novel mechanistic insights and may inform precision approaches to drug development, biomarker discovery, and clinical trial design for AD.

The Toxicology Investigators Consortium 2024 Annual Report - Kim Aldy; Shao Li; Mari Costantini; Alyssa Falise; Rachel Culbreth; Paul M. Wax; Jeffery Brent; Michael Abesamis; Faiz Ahmed; Salman Ahsan; Peter Akpunonu; Adam Algren; et al. (Journal of Medical Toxicology, 2026)

Dynamic of infectious aerosols generated by cough from patients with pulmonary tuberculosis - Taline Canto Tristão; Mariana Abou Mourad Ferreira; Pedro Sousa de Almeida Júnior; Luiz Guilherme Schmidt Castellani; Manuela Negrelli Brunetti; Edward C. Jones-López; Kevin P. Fennelly; Michael R. Barer; Carlos Henrique Fantecelle; Saulo Almeida Morellato; David Jamil Hadad; Jerrold J. Ellner; et al. (Journal of Aerosol Science, 2025)

Spatially resolved X-ray imaging and molecular characterisation of sulfur and iron in organic- and sulfur-rich hydrocarbon source mudstones - Yusuf Abubakar; Roy A. Wogelius; Victoria S. Coker; Kevin G. Taylor; Nicholas P. Edwards; Bart E. van Dongen (Chemical Geology, 2025)

A Narrative Review on the Neuroprotective Effects of Selenium and Vitamin D in Alzheimer’s Disease - Edward Kevin Bragais; Kim Leonard dela Luna; Vanessa Joy Timoteo-Garcia (Biological Trace Element Research, 2025)

Community-onset bloodstream infection among people with opioid use disorders: a twenty-year population-based cohort study in Queensland, Australia - Kevin B. Laupland; Adam G. Stewart; Felicity Edwards; Patrick N. A. Harris; Sonali Coulter (Infectious Diseases, 2025)

Determinants of time to positivity in bloodstream infections: an analysis of a population-based cohort in Queensland, Australia - Felicity Edwards; Michael Waller; Kevin B. Laupland (European Journal of Clinical Microbiology & Infectious Diseases, 2025)
Purpose Time to Positivity (TTP) measures the interval from incubation to bacterial growth detection in blood cultures. Although shorter TTP is associated with higher mortality, factors associated with TTP remain uncertain. Methods A retrospective cohort study was conducted among Queensland residents with positive blood cultures between 2000–2019. Incident bloodstream infections (BSIs) were identified using Pathology Queensland data, with demographic, clinical, and outcome data linked to state-wide databases. Results The study analysed 84,341 patients with monomicrobial BSI with a median patient age of 65.6 years (IQR 45.4–78.1), and most infections being community-associated (77.0%). Age showed a non-linear relationship with TTP, and male sex was linked with slightly higher TTP (Incidence Rate Ratio (IRR) 1.01; 95% Confidence Intervals (CI) 1.00–1.02; p = 0.011), reflecting a small but measurable association. Liver disease and malignancy were associated with lower TTP (IRR 0.93; 95% CI 0.91–0.95; p < 0.0001 and IRR 0.95; 95% CI 0.94–0.97; p < 0.0001 respectively), whilst diabetes showed no significant difference (IRR 1.01; 95% CI 1.00–1.02; p = 0.0840). Hospital onset infections exhibited longer TTPs (IRR 1.09; 95% CI 1.08–1.10; p < 0.0001). Conclusions There are several host characteristics associated with TTP that may in part explain the complex relationship between this variable and mortality. Beyond microbiological factors such as isolate type, TTP is also influenced by clinical variables including patient demographics and infection characteristics highlighting its potential as a prognostic marker. Further evaluation is needed to clarify its role in predicting patient outcomes and guiding tailored treatment strategies.

BioTIME 2.0: Expanding and Improving a Database of Biodiversity Time Series - Maria Dornelas; Laura H. Antão; Amanda E. Bates; Viviana Brambilla; Jonathan M. Chase; Cher F. Y. Chow; Ada Fontrodona‐Eslava; Anne E. Magurran; Inês S. Martins; Faye Moyes; Alban Sagouis; Samuel Adu‐Acheampong; et al. (Global Ecology and Biogeography, 2025)
Motivation Here, we make available a second version of the BioTIME database, which compiles records of abundance estimates for species in sample events of ecological assemblages through time. The updated version expands version 1.0 of the database by doubling the number of studies and includes substantial additional curation to the taxonomic accuracy of the records, as well as the metadata. Moreover, we now provide an R package (BioTIMEr) to facilitate use of the database. Main Types of Variables Included The database is composed of one main data table containing the abundance records and 11 metadata tables. The data are organised in a hierarchy of scales where 11,989,233 records are nested in 1,603,067 sample events, from 553,253 sampling locations, which are nested in 708 studies. A study is defined as a sampling methodology applied to an assemblage for a minimum of 2 years. Spatial Location and Grain Sampling locations in BioTIME are distributed across the planet, including marine, terrestrial and freshwater realms. Spatial grain size and extent vary across studies depending on sampling methodology. We recommend gridding of sampling locations into areas of consistent size. Time Period and Grain The earliest time series in BioTIME start in 1874, and the most recent records are from 2023. Temporal grain and duration vary across studies. We recommend doing sample‐level rarefaction to ensure consistent sampling effort through time before calculating any diversity metric. Major Taxa and Level of Measurement The database includes any eukaryotic taxa, with a combined total of 56,400 taxa. Software Format csv and. SQL.

Predicting the progression of MCI and Alzheimer’s disease on structural brain integrity and other features with machine learning - Marthe Mieling; Mushfa Yousuf; Nico Bunzeck; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; Susan Landau; Monica Rivera-Mindt; Leslie M. Shaw; Edward B. Lee; et al. (GeroScience, 2025)
Machine learning (ML) on structural MRI data shows high potential for classifying Alzheimer’s disease (AD) progression, but the specific contribution of brain regions, demographics, and proteinopathy remains unclear. Using Alzheimer’s Disease Neuroimaging Initiative (ADNI) data, we applied an extreme gradient-boosting algorithm and SHAP (SHapley Additive exPlanations) values to classify cognitively normal (CN) older adults, those with mild cognitive impairment (MCI) and AD dementia patients. Features included structural MRI, CSF status, demographics, and genetic data. Analyses comprised one cross-sectional multi-class classification (CN vs. MCI vs. AD dementia, n = 568) and two longitudinal binary-class classifications (CN-to-MCI converters vs. CN stable, n = 92; MCI-to-AD converters vs. MCI stable, n = 378). All classifications achieved 70–77% accuracy and 61–83% precision. Key features were CSF status, hippocampal volume, entorhinal thickness, and amygdala volume, with a clear dissociation: hippocampal properties contributed to the conversion to MCI, while the entorhinal cortex characterized the conversion to AD dementia. The findings highlight explainable, trajectory-specific insights into AD progression.

Sedimentary records of late Pleistocene-Holocene paleoenvironments from Convict Lake (California, USA) - Bailee N. Hodelka; Morgan Black; Adam J. Benfield; Sarah J. Ivory; Edward W. Woolery; Kevin Woller; Susan R.H. Zimmerman; Michael M. McGlue (Quaternary International, 2025)

Ultraviolet radiation vs air filtration to mitigate virus laden aerosol in an occupied clinical room - Shane A. Landry; Milan Jamriska; Vinay J. Menon; Leo Yi Yang Lee; Isabelle Magnin-Bougma; Dinesh Subedi; Jeremy J. Barr; Jason Monty; Kevin Kevin; Ajith Gunatilaka; Michelle Delaire; Guy B. Marks; et al. (Journal of Hazardous Materials, 2025)

Multi‐Species Telemetry Quantifies Current and Future Efficacy of a Remote Marine Protected Area - Morgan E. Gilmour; Kydd Pollock; Josh Adams; Barbara A. Block; Jennifer E. Caselle; Alex Filous; Alan M. Friedlander; Edward T. Game; Elliott L. Hazen; Marie Hill; Nick D. Holmes; Kevin D. Lafferty; et al. (Global Change Biology, 2025)
Large‐scale marine protected areas (LSMPAs; > 1000 km 2 ) provide important refuge for large mobile species, but most do not encompass species' ranges. To better understand current and future LSMPA value, we concurrently tracked nine species (seabirds, cetaceans, pelagic fishes, manta rays, reef sharks) at Palmyra Atoll and Kingman Reef (PKMPA) in the U.S. Pacific Islands Heritage Marine National Monument. PKMPA and the U.S. Exclusive Economic Zone encompassed 39% and 54% of species movements ( n = 83; tracking duration range: 0.5–350 days), respectively. Species distribution models indicated 73% of PKMPA contained highly suitable habitat. Under two projected future scenarios (SSP 1–2.6, “Sustainability”; SSP 3–7.0, “Rocky Road”), strong sea surface temperature gradients initially could cause abrupt oceanic change resulting in predicted habitat loss in 2040–2050, followed by an equilibrium response and regained habitat by 2090–2100. Current and future suitable habitats were available adjacent to PKMPA, suggesting that increased MPA size could enhance protection. Our three‐tiered approach combining animal tracking with publicly available remote sensing data and future projected environmental scenarios could be used to design, study, and monitor protected areas throughout the world. Holistic approaches that encompass diverse species and habitat use can enhance assessments of protected area designs. Animal telemetry and remote sensing may be helpful for ascertaining the extent to which other MPAs protect large mobile species in the future.

Risk of mortality in Fusobacterium species bloodstream infection from a large Australian cohort - Adam G. Stewart; Felicity Edwards; Patrick N. A. Harris; David L. Paterson; Kevin B. Laupland (European Journal of Clinical Microbiology & Infectious Diseases, 2025)

Ensuring accurate microclimate research: How to select representative meteorological data of local climate in microclimate studies - Kai Gao; Jie Feng; Lingye Yao; Kevin Lau; Edward Ng (Building and Environment, 2025)

Suitable temperature indicator for adverse health impacts in sub-tropical cities: a case study in Hong Kong from 2010-2019 - Janice Ying-en Ho; Yitong Guo; Ka Chun Chong; Pak Wai Chan; Chun Kit Ho; Hiu Fai Law; Ren Chao; Edward Yan Yung Ng; Kevin Lau (International Journal of Biometeorology, 2025)
Heat-health warning systems and services are important preventive actions for extreme heat, however, global evidence differs on which temperature indicator is more informative for heat-health outcomes. We comprehensively assessed temperature predictors on their summer associations with adverse health impacts in a high-density subtropical city. Maximum, mean, and minimum temperatures were examined on their associations with non-cancer mortality and hospital admissions in Hong Kong during summer seasons 2010–2019 using Generalized Additive Models and Distributed Lag Non-linear Models. In summary, mean and minimum temperatures were identified as strong indicators for mortality, with a relative risk(RR) and 95% confidence interval(CI) of 1.037 (1.006–1.069) and 1.055 (1.019–1.092), respectively, at 95th percentile vs. optimal temperature. Additionally, minimum temperatures captured the effects of hospital admissions, RR1.009 (95%CI: 1.000- 1.018). In stratified analyses, significant associations were found for older adults, female sex, and respiratory-related outcomes. For comparison, there was no association between maximum temperature and health outcomes. With climate change and projected increase of night-time warming, the findings from this comprehensive assessment method are useful to strengthen heat prevention strategies and enhance heat-health warning systems. Other locations could refer to this comprehensive method to evaluate their heat risk, especially in highly urbanized environments and subtropical cities.

Formation of vertical columnar seismic structures and seafloor depressions by groundwater discharge in the drowned Miami Terrace platform and overlying deep-water carbonates, southeastern Florida - Kevin J. Cunningham; Richard L. Westcott; Sean Norgard; Edward Robinson; Harry J. Dowsett; Marci M. Robinson (Marine Geology, 2024)

Hydrogen-induced mineral alteration: A review in the context of underground hydrogen storage (UHS) in saline aquifers - Heather Braid; Kevin Taylor; Edward Hough; Chris Rochelle; Vahid Niasar; Lin Ma (Earth-Science Reviews, 2024)

The Toxicology Investigators Consortium 2023 Annual Report - Adrienne Hughes; Alexandra Amaducci; Sharan L. Campleman; Shao Li; Mari Costantini; Meghan B. Spyres; Hannah Spungen; Jessica Kent; Alyssa Falise; Rachel Culbreth; Paul M. Wax; Jeffery Brent; et al. (Journal of Medical Toxicology, 2024)

Epidemiology of biliary tract-associated bloodstream infections and adequacy of empiric therapy: an Australian population-based study - Ian Gassiep; Felicity Edwards; Kevin B. Laupland (European Journal of Clinical Microbiology & Infectious Diseases, 2024)
Purpose Although the biliary tract is a common source of invasive infections, the epidemiology of cholangitis- and cholecystitis-associated bloodstream infection (BSI) is not well defined. The objective of this study was to determine the incidence, clinical determinants, microbiology of biliary tract-associated BSI, and predicted adequacy of common empiric therapy regimens. Methods All biliary tract-associated BSI in Queensland during 2000–2019 were identified using state-wide data sources. Predicted adequacy of empiric antimicrobial therapy was determined according to microbiological susceptibility data. Results There were 3,698 episodes of biliary tract-associated BSI occurred in 3,433 patients of which 2,147 (58.1%) episodes were due to cholangitis and 1,551 (41.9%) cholecystitis, for age- and sex-standardized incidence rates of 2.7, and 2.0 per 100,000 population, respectively. An increasing incidence of biliary tract-associated BSI was observed over the study that was attributable to an increase in cholangitis cases. There was a significant increased risk for biliary tract-associated BSI observed with advancing age and male sex. Patients with cholangitis were older, more likely to have healthcare associated infection, and have more comorbidities most notably liver disease and malignancies as compared to patients with cholecystitis. The distribution of infecting pathogens was significantly different with polymicrobial aetiologies more commonly observed with cholangitis (18.4% vs. 10.5%; p < 0.001). The combination of ampicillin/gentamicin/metronidazole was predicted to have the overall highest adequacy (96.1%), whereas amoxicillin/clavulanate had the lowest (77.0%). Amoxicillin/clavulanate (75.2% vs. 79.4%, p:0.03) and ceftriaxone/metronidazole (83.4% vs. 89.6%; p < 0.001) showed significantly inferior predicted adequacy for cholangitis as compared to cholecystitis. Conclusions Bloodstream infections related to cholecystitis and cholangitis exhibit different epidemiology, microbiology, and requirements for empiric therapy.

Pseudomonas stutzeri bloodstream infection is a prevailing community-onset disease with important mortality rates: results from a retrospective observational study in Australia - Juan P. Horcajada; Felicity Edwards; Silvia Fonio; Milagro Montero; Patrick Harris; David L. Paterson; Kevin B. Laupland (Infectious Diseases, 2024)

Topical Solution for Retinal Delivery: Bevacizumab and Ranibizumab Eye Drops in Anti-Aggregation Formula (AAF) in Rabbits - Steven A. Giannos; Edward R. Kraft; Jonathan D. Luisi; Mary E. Schmitz-Brown; Valentina Reffatto; Kevin H. Merkley; Praveena K. Gupta (Pharmaceutical Research, 2024)
Purpose Wet age-related macular degeneration (AMD) is a blinding retinal disease. Monthly intravitreal anti-VEGF antibody injections of bevacizumab (off-label) and ranibizumab (FDA approved) are the standard of care. Antibody aggregation may interfere with ocular absorption/distribution. This study assessed topical delivery of dilute antibodies to the posterior segment of rabbit eyes using a novel anti-aggregation formula (AAF). Methods Bevacizumab, or biosimilar ranibizumab was diluted to 5 mg/ml in AAF. All rabbits were dosed twice daily. Substudy 1 rabbits (bevacizumab, 100 µl eye drops): Group 1 (bevacizumab/AAF, n = 6); Group 2 (bevacizumab/PBS, n = 7) and Vehicle control (AAF, n = 1). Substudy 2 rabbits (ranibizumab biosimilar/AAF, 50 µl eye drops): (ranibizumab biosimilar/AAF, n = 8). At 14.5 days, serum was drawn from rabbits. Aqueous, vitreous and retina samples were recovered from eyes and placed into AAF aliquots. Tissue analyzed using AAF as diluent. Results Bevacizumab in AAF permeated/accumulated in rabbit aqueous, vitreous and retina 10 times more, than when diluted in PBS. AAF/0.1% hyaluronic acid eye drops, dosed twice daily, provided mean tissue concentrations (ng/g) in retina (29.50), aqueous (12.34), vitreous (3.46), and serum (0.28 ng/ml). Additionally, the highest concentration (ng/g) of ranibizumab biosimilar was present in the retina (18.0), followed by aqueous (7.82) and vitreous (1.47). Serum concentration was negligible (< 0.04 ng/ml). No irritation was observed throughout the studies. Conclusions Bevacizumab and ranibizumab, in an AAF diluent eye drop, can be delivered to the retina, by the twice daily dosing of a low concentration mAb formulation. This may prove to be an adjunct to intravitreal injections.

RelA-mediated signaling connects adaptation to chronic cardiomyocyte stress with myocardial and systemic inflammation in the ADCY8 model of accelerated aging - Vikas Kumar; Kevin Christian Bermea; Dhaneshwar Kumar; Amit Singh; Anjali Verma; Mary Kaileh; Ranjan Sen; Edward G. Lakatta; Luigi Adamo (GeroScience, 2024)

Surface ocean warming near the core of hurricane Sam and its representation in forecast models - Andrew M. Chiodi; Hristina Hristova; Gregory R. Foltz; Jun A. Zhang; Calvin W. Mordy; Catherine R. Edwards; Chidong Zhang; Christian Meinig; Dongxiao Zhang; Edoardo Mazza; Edward D. Cokelet; Eugene F. Burger; et al. (Frontiers in Marine Science, 2024)
On September 30, 2021, a saildrone uncrewed surface vehicle intercepted Hurricane Sam in the northwestern tropical Atlantic and provided continuous observations near the eyewall. Measured surface ocean temperature unexpectedly increased during the first half of the storm. Saildrone current shear and upper-ocean structure from the nearest Argo profiles show an initial trapping of wind momentum by a strong halocline in the upper 30 m, followed by deeper mixing and entrainment of warmer subsurface water into the mixed layer. The ocean initial conditions provided to operational forecast models failed to capture the observed upper-ocean structure. The forecast models failed to simulate the warming and developed a surface cold bias of ~0.5°C by the time peak winds were observed, resulting in a 12-17% underestimation of surface enthalpy flux near the eyewall. Results imply that enhanced upper-ocean observations and, critically, improved assimilation into the hurricane forecast systems, could directly benefit hurricane intensity forecasts.

‘The man who vacuum cleaned the Atlantic’ − the aerosol collector and Gunnar Erdtman’s attempts to measure pollen rain - Kevin J. Edwards; Pia Östensson (Palynology, 2024)

Balancing thermal comfort and energy efficiency in high-rise public housing in Hong Kong: Insights and recommendations - Kai Gao; K.F. Fong; C.K. Lee; Kevin Ka-Lun Lau; Edward Ng (Journal of Cleaner Production, 2024)

Experimental characterization of the low-temperature thermal decomposition of diisopropyl methylphosphonate (DIMP) - Elif Irem Senyurt; Kevin Watson; Andrea C. Zambon; Gregory Feldman; Neeraj Sinha; Vern K. Hoffmann; Mirko Schoenitz; Edward L. Dreizin (Chemical Engineering Journal, 2024)

Ecosystem feedbacks constrain the effect of day‐to‐day weather variability on land–atmosphere carbon exchange - Edward B. Rastetter; Kevin L. Griffin; Bonnie L. Kwiatkowski; George W. Kling (Global Change Biology, 2023)
Whole‐ecosystem interactions and feedbacks constrain ecosystem responses to environmental change. The effects of these constraints on responses to climate trends and extreme weather events have been well studied. Here we examine how these constraints respond to changes in day‐to‐day weather variability without changing the long‐term mean weather. Although environmental variability is recognized as a critical factor affecting ecological function, the effects of climate change on day‐to‐day weather variability and the resultant impacts on ecosystem function are still poorly understood. Changes in weather variability can alter the mean rates of individual ecological processes because many processes respond non‐linearly to environmental drivers. We assessed how these individual‐process responses to changes in day‐to‐day weather variability interact with one another at an ecosystem level. We examine responses of arctic tundra to changes in weather variability using stochastic simulations of daily temperature, precipitation, and light to drive a biogeochemical model. Changes in weather variability altered ecosystem carbon, nitrogen, and phosphorus stocks and cycling rates in our model. However, responses of some processes (e.g., respiration) were inconsistent with expectations because ecosystem feedbacks can moderate, or even reverse, direct process responses to weather variability. More weather variability led to greater carbon losses from land to atmosphere; less variability led to higher carbon sequestration on land. The magnitude of modeled ecosystem response to weather variability was comparable to that predicted for the effects of climate mean trends by the end of the century.

Free-water imaging reveals unique brain microstructural deficits in hispanic individuals with Dementia - Edward Ofori; David E. Vaillancourt; Maria T Greig-Custo; Warren Barker; Kevin Hanson; Steven T. DeKosky; Cynthia S. Garvan; Malek Adjouadi; Todd Golde; David A. Loewenstein; Chad Stecher; Rylan Fowers; et al. (Brain Imaging and Behavior, 2023)

The Toxicology Investigators Consortium 2022 Annual Report - Alexandra M. Amaducci; Sharan L. Campleman; Shao Li; Dana L. Karshenas; Meghan B. Spyres; Lynn A. Farrugia; A. Min Kang; Rachel E. Culbreth; Paul M. Wax; Jeffrey Brent; Kim Aldy; Jennifer Acciani; et al. (Journal of Medical Toxicology, 2023)

Mechanisms and models for industry engagement in collaborative research in commercial fisheries - Matthew R. Baker; Robert Alverson; Ruth Christiansen; Keith Criddle; Danny Eilertsen; Robert J. Foy; John Gauvin; Scott E. Goodman; Leigh Habegger; Bradley P. Harris; Nicole Kimball; Anna Malek Mercer; et al. (Frontiers in Marine Science, 2023)
Data and insights from fishers are essential sources of information to advance understanding of fishery and ecosystem dynamics. Incorporating fisher and industry knowledge holds prospects for improving marine science and fisheries management. We address cooperative research in the context of collaboration between fishers, scientists, industries, universities, and agencies to develop applied research to understand marine ecosystems, inform fishery management, enhance sustainability, govern resource use, and investigate social-economic dynamics. We leverage the insights of more than 100 research scientists, fisheries managers, industry representatives, and fishers to outline actionable recommendations for effective approaches and mechanisms to integrate industry data, perspectives, and insights in fisheries science. We also highlight opportunities and address challenges and limitations to such collaboration.

Evaluation on the performance of tree view factor in a high-density subtropical city: A case study in Hong Kong - Ka Yuen Cheng; Kevin Lau; Ying Ting Shek; Zhixin Liu; Edward Ng (Building and Environment, 2023)

Community‐based monitoring, assessment and management of data‐limited inland fish stocks in North Rupununi, Guyana - Samuel Shephard; Kevin Edwards; Susan George; Elvis Joseph; Samantha James; Oswin David; Addevi Persaud; L. Cynthia Watson; Nathalie Van Vliet (Fisheries Management and Ecology, 2023)
Inland fisheries are important for food security in communities around the world, especially in developing countries. In North Rupununi, Guyana, the state of exploited stocks is poorly understood, and fishery monitoring and assessment are challenging because diverse fishing gears and target species are distributed across a heterogeneous landscape. This complexity created an opportunity for community‐based monitoring (CBM) to support data‐limited assessment. Standardised CBM was established for the North Rupununi as part of a new inland fisheries management plan initiated by indigenous community groups with support from the government. Quantitative length‐based assessments undertaken for target stocks suggested moderate levels of exploitation consistent with local perception. Our study highlights that local experts and community participants with different levels of training can collect accurate biodiversity data. Further development of CBM is important in North Rupununi. We recommend using local ecological knowledge indicators to track spatial and temporal patterns in exploitation and fish stock status.

Urban heat island effect-related mortality under extreme heat and non-extreme heat scenarios: A 2010–2019 case study in Hong Kong - Janice Y. Ho; Yuan Shi; Kevin K.L. Lau; Edward Y.Y. Ng; Chao Ren; William B. Goggins (Science of The Total Environment, 2023)

Evolving insights into the epidemiology of Moraxella species bloodstream infection from two decades of surveillance in Queensland, Australia - Jessica Schults; Felicity Edwards; Karina Charles; Adam D. Irwin; Claire M. Rickard; Patrick N. A. Harris; David L. Paterson; Kevin Laupland (European Journal of Clinical Microbiology & Infectious Diseases, 2023)

Determinants and outcomes of bloodstream infections related to obesity - Felicity Edwards; Kate Glen; Patrick N. A. Harris; David L. Paterson; Kevin B. Laupland (European Journal of Clinical Microbiology & Infectious Diseases, 2022)
Although obesity is a major healthcare problem that is increasing in many populations worldwide, there are limited studies that have examined its contribution to infectious diseases morbidity and mortality. The aim of this study was to examine the clinical determinants and outcomes of bloodstream infections among patients with obesity. All adults within the publicly funded healthcare system in Queensland, Australia, identified with a BSI during 2017–2019 were included and the presence of obesity was based on discharge International Classification of Diseases (ICD-10) codes. Clinical features, microbiology, and outcomes were compared among obese and non-obese subjects. A total of 24,602 incident BSI were identified among 21,613 Queensland residents; of which 4,579 (21.2%) and 17,034 (78.8%) were classified as obese or non-obese, respectively. Obese patients were less likely to have community associated infections and were more likely to be younger, female, have higher comorbidity scores, and have bone and joint or soft tissue infections as compared to non-obese subjects. Obese patients had a lower proportion of Escherichia coli BSI and higher proportions of b-haemolytic streptococci. Although obese patients had longer hospital admissions and more repeat incident BSI within 1 year, they had lower overall case fatality. In a logistic regression model, obesity was associated with a lower risk for 30-day case fatality (adjusted odds ratio 0.51, 95% confidence interval 0.45–0.58). Obesity is associated with significant differences in the determinants and outcome of BSI. Increasing rates of obesity is likely to influence the epidemiology of BSI in populations.

The Toxicology Investigators Consortium Case Registry—the 2021 Annual Report - Jennifer S. Love; Dana L. Karshenas; Meghan B. Spyres; Lynn A. Farrugia; A. Min Kang; HoanVu Nguyen; Sharan L. Campleman; Shao Li; Paul M. Wax; Jeffery Brent; Kim Aldy; Michael Abesamis; et al. (Journal of Medical Toxicology, 2022)

Development of the invasive candidiasis discharge [I Can discharge] model: a mixed methods analysis - Jinhee Jo; Truc T. Tran; Nicholas D. Beyda; Debora Simmons; Joshua A. Hendrickson; Masaad Saeed Almutairi; Faris S. Alnezary; Anne J. Gonzales-Luna; Edward J. Septimus; Kevin W. Garey (European Journal of Clinical Microbiology & Infectious Diseases, 2022)
Patients with invasive candidiasis (IC) have complex medical and infectious disease problems that often require continued care after discharge. This study aimed to assess echinocandin use at hospital discharge and develop a transition of care (TOC) model to facilitate discharge for patients with IC. This was a mixed method study design that used epidemiologic assessment to better understand echinocandin use at hospital discharge TOC. Using grounded theory methodology focused on patients given echinocandins during their last day of hospitalization, a TOC model for patients with IC, the invasive candidiasis [I Can] discharge model was developed to better understand discharge barriers. A total of 33% (1405/4211) echinocandin courses were continued until the last day of hospitalization. Of 536 patients chosen for in-depth review, 220 (41%) were discharged home, 109 (20%) were transferred, and 207 (39%) died prior to discharge. Almost half (46%, 151/329) of patients discharged alive received outpatient echinocandin therapy. Independent predictors for outpatient echinocandin use were osteomyelitis (OR, 4.1; 95% CI, 1.1–15.7; p = 0.04), other deep-seated infection (OR, 4.4; 95% CI, 1.7–12.0; p = 0.003), and non-home discharge location (OR, 3.9, 95% CI, 2.0–7.7; p < 0.001). The I Can discharge model was developed encompassing four distinct themes which was used to identify potential barriers to discharge. Significant echinocadin use occurs at hospital discharge TOC. The I Can discharge model may help clinical, policy, and research decision-making processes to facilitate smoother and earlier hospital discharges.

Multi-year acoustic tracking reveals transient movements, recurring hotspots, and apparent seasonality in the coastal-offshore presence of Greenland sharks (Somniosus microcephalus) - Jena E. Edwards; Kevin J. Hedges; Steven T. Kessel; Nigel E. Hussey (Frontiers in Marine Science, 2022)
Variable movement strategies can complicate the conservation and management of mobile species. Given its extreme life history traits as a long-lived, deep-water species, the Greenland shark ( Somniosus microcephalus ) is vulnerable to fisheries bycatch, but little is known over its long-term movements across a spatially and seasonally variable Arctic environment. To address this knowledge gap, the movements of Greenland sharks in coastal fjords and offshore waters of Baffin Bay were examined using seven years of acoustic telemetry data. Seasonal patterns in broad-scale movements and inshore-offshore connectivity were compared among 155 sharks (101 males, 54 females [mean LT = 2.65 ± 0.48 m, range 0.93-3.5 m]) tagged in 6 discrete coastal locations spanning from Grise Fiord to Cumberland Sound (Nunavut). Sharks exhibited transient movements throughout coastal and offshore regions with some evidence of seasonally recurring hotspots revealed by repeat detections of individuals at sites over multiple years. Shark presence in coastal fjords occurred exclusively during the coastal ice-free period (July to November), regardless of the location of tagging or detection, while presence in the offshore was recorded during the period of ice re-formation and cover (November to July). Through multi-year telemetry, it was possible to reveal repetitive patterns in broad-scale habitat use for a complex marine predator with direct relevance for understanding the seasonal distribution of mobile Arctic consumers and informing regional fisheries management.

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Pasteurella species bloodstream infections in Queensland, Australia, 2000–2019 - Kevin B. Laupland; Adam G. Stewart; Felicity Edwards; Patrick Harris; Claire Heney; Narelle George; Sonali Coulter; David L. Paterson (European Journal of Clinical Microbiology & Infectious Diseases, 2022)
Pasteurella species are infrequent but potentially severe causes of bloodstream infection (BSI). The objective of this study was to determine the incidence, risk factors, and outcomes of Pasteurella species BSI in a large Australian population. Retrospective, laboratory-based surveillance was conducted in Queensland, Australia (population ≈ 5 million) during 2000–2019, and clinical and outcome information was established by linkage to state hospital admissions and vital statistics databases. During more than 86 million person-years of surveillance, 272 incident Pasteurella species BSI occurred for an overall age- and sex-standardized annual incidence of 3.3 per million residents. The incidence of Pasteurella species BSI was highest in recent years and older individuals were at greatest risk. The median (interquartile range) Charlson Comorbidity Index was 2 (0–4) with scores of zero, 1, 2, and 3 + observed in 81 (30%), 37 (14%), 44 (16%), and 110 (40%) of cases. The 30-day all-cause case fatality was 9% (24/272) and patients who died had more comorbidities and were less likely to have community-associated disease. Although Pasteurella species are infrequent causes of BSI, older individuals and those with comorbidities are at highest risk. The burden of this disease may be expected to increase with an aging and more comorbid population.

‘The most remarkable man’: James Croll, Quaternary scientist - Kevin J. Edwards (Journal of Quaternary Science, 2022)
The year 2021 marked the bicentenary of the birth of James Croll (1821–1890), the self‐educated son of a crofter‐stonemason, whose life was characterised by a dizzying range of occupations and homes, poor health and financial concerns, and yet he became a pioneer of orbital dynamics and ice age climate change with an impressive record of publication. Drawing upon archival information and recently published observations, this paper explores selected aspects of Croll's biography, his scientific connections and controversies, and that area of his life relevant to Quaternary science. He was a 19th century polymath whose multifaceted contributions have been a catalyst for subsequent systems‐based climate science on the grand scale, including the foundations for the seminal work of Milutin Milankovitch on the rhythms of Quaternary environmental change.

Mesozooplankton Community Dynamics and Grazing Potential Across Algal Bloom Cycles in a Subtropical Estuary - L. Holly Sweat; Hunter Alexander; Edward J. Phlips; Kevin B. Johnson (Frontiers in Marine Science, 2021)
Mesozooplankton, as abundant grazers of microalgae in coastal systems, have the potential to prevent or mitigate harmful algal blooms (HABs) and their effects. The Indian River Lagoon (IRL) is a subtropical estuary in eastern Florida (United States) where repeated blooms, dominated by the toxic dinoflagellate Pyrodinium bahamense , the brown tide species Aureoumbra lagunensis , pico/nano planktonic cyanobacteria and other nano-eukaryotes, have highlighted the need to better understand fluctuations in the grazing potential of mesozooplankton populations across bloom cycles. Mesozooplankton and abiotic environmental data were collected at five sites in the northern IRL system at 6-week intervals from November 2013 through June 2016. A total of 107 taxa from 14 phyla were detected. Communities varied across sites, dates and between bloom and non-bloom periods, with densities up to 338 individuals L –1 . Eight taxa comprising 85–94% of the total population at each site were identified as primary potential grazers, including barnacle nauplii, cladocerans, adult copepods, gastropod veligers, larvaceans, and polychaete metatrochophores. Although abundant, the estimated grazing potential of the primary taxa, calculated from their measured densities and previously published grazing rates, suggest that mesozooplankton lack the capacity to suppress phytoplankton once they reach bloom levels. These findings illustrate the utility of monitoring data and underscore the importance of systematically evaluating algal bloom controls with a consideration for the dynamic conditions of each unique ecosystem.

Estimating fine‐scale movement rates and habitat preferences using multiple data sources - James T. Thorson; Steven J. Barbeaux; Daniel R. Goethel; Kelly A. Kearney; Edward A. Laman; Julie K. Nielsen; Matthew R. Siskey; Kevin Siwicke; Grant G. Thompson (Fish and Fisheries, 2021)
Fisheries scientists and managers must track rapid shifts in fish spatial distribution to mitigate stakeholder conflict and optimize survey designs, and these spatial shifts result in part from animal movement. Information regarding animal movement can be obtained from selection experiments, tagging studies, flux through movement gates (e.g. acoustic arrays), fishery catch‐per‐unit effort (CPUE), resource surveys and genetic/chemical markers. However, there are few accessible approaches to combine these data types while accounting for spatially correlated residual patterns. We therefore discuss a movement model involving diffusion (random movement), taxis (movement towards preferred habitat) and advection (passive drift following ocean currents). We specifically outline how these movement processes can be fitted to data while discretizing space and time and estimating non‐linear habitat preferences using environmental layers as well as spatial process errors. Finally, we introduce an R package, ATM, by fitting the model to bottom trawl survey, longline fishery and tagging data for Pacific cod ( Gadus macrocephalus , Gadidae) in the Bering Sea during winter/summer seasons from 1982 to 2019. Combining data types predicts an increasing proportion of cod residing in the northern Bering Sea from 2013 to 2019, and estimates are informative in a recent stock assessment model. We fit sensitivity analyses by dropping tag, survey or fishery data, and this analysis shows that tagging data are necessary to identify diffusion rates, while survey data are informative about movement among biogeographic strata. This “hybrid” species distribution model can help explain poleward movement, project distributions under future climate conditions and evaluate alternative tag‐deployment scenarios to optimize tagging designs.

Effects of sustained GABA releasing implants on pancreatic islets in mice - Kevin C. Ling; D. Walker Hagan; Jorge Santini-González; Edward A. Phelps (Drug Delivery and Translational Research, 2021)

William Su Ting – China’s forgotten palynologist - Kevin J. Edwards; Limi Mao (Palynology, 2021)

Microbial biogeography through the lens of exotic species: the recent introduction and spread of the freshwater diatom Discostella asterocostata in the United States - Andrew J. Alverson; Tyler K. Chafin; Kiley A. Jones; Kalina M. Manoylov; Hillary Johnson; Matthew L. Julius; Teofil Nakov; Elizabeth C. Ruck; Edward C. Theriot; Kevin M. Yeager; Jeffery R. Stone (Biological Invasions, 2021)

Exploring the Pacific Arctic Seasonal Ice Zone With Saildrone USVs - Andrew M. Chiodi; Chidong Zhang; Edward D. Cokelet; Qiong Yang; Calvin W. Mordy; Chelle L. Gentemann; Jessica N. Cross; Noah Lawrence-Slavas; Christian Meinig; Michael Steele; Don E. Harrison; Phyllis J. Stabeno; et al. (Frontiers in Marine Science, 2021)
More high-quality, in situ observations of essential marine variables are needed over the seasonal ice zone to better understand Arctic (or Antarctic) weather, climate, and ecosystems. To better assess the potential for arrays of uncrewed surface vehicles (USVs) to provide such observations, five wind-driven and solar-powered saildrones were sailed into the Chukchi and Beaufort Seas following the 2019 seasonal retreat of sea ice. They were equipped to observe the surface oceanic and atmospheric variables required to estimate air-sea fluxes of heat, momentum and carbon dioxide. Some of these variables were made available to weather forecast centers in real time. Our objective here is to analyze the effectiveness of existing remote ice navigation products and highlight the challenges and opportunities for improving remote ice navigation strategies with USVs. We examine the sources of navigational sea-ice distribution information based on post-mission tabulation of the sea-ice conditions encountered by the vehicles. The satellite-based ice-concentration analyses consulted during the mission exhibited large disagreements when the sea ice was retreating fastest (e.g., the 10% concentration contours differed between analyses by up to ∼175 km). Attempts to use saildrone observations to detect the ice edge revealed that in situ temperature and salinity measurements varied sufficiently in ice bands and open water that it is difficult to use these variables alone as a reliable ice-edge indicator. Devising robust strategies for remote ice zone navigation may depend on developing the capability to recognize sea ice and initiate navigational maneuvers with cameras and processing capability onboard the vehicles.

Ecosystem Recovery from Disturbance is Constrained by N Cycle Openness, Vegetation-Soil N Distribution, Form of N Losses, and the Balance Between Vegetation and Soil-Microbial Processes - Edward B. Rastetter; George W. Kling; Gaius R. Shaver; Byron C. Crump; Laura Gough; Kevin L. Griffin (Ecosystems, 2021)

Palynological evidence for pre-agricultural reindeer grazing and the later settlement history of the Lycksele region, northern Sweden - Ilse M. Kamerling; J. Edward Schofield; Kevin J. Edwards (Archaeological and Anthropological Sciences, 2021)
Analyses of high-resolution pollen data, coprophilous fungal spores, microscopic charcoal and sedimentology, combined with radiocarbon dating, allow the assessment of the impact of Sami and Nordic land use in the region surrounding the winter market town of Lycksele in northern Sweden. Such winter markets were established by the Crown during the seventeenth century AD to control the semi-nomadic movements of the Sami who traded here with Finnish settlers and were also taxed and educated. Little is known about Sami and Nordic co-existence beyond these market places, mainly due to a lack of archaeological evidence relating to Sami activity. Vegetation and land-use changes in the region between ~ AD 250 and 1825 reveal no signal for pre-seventeenth century agricultural activity, but the coprophilous fungal spore records suggest the increased regional presence of grazing herbivores (possibly reindeer) between ~ AD 800 and 1100. Sami activity in the parish of Lycksele has been suggested by rich metal finds dated to ~ AD 1000–1350 and they may have been attracted by an abundance of reindeer.

A marine teleost, Opsanus beta, compensates acidosis in hypersaline water by H+ excretion or reduced HCO3− excretion rather than HCO3− uptake - Zongli Yao; Kevin L. Schauer; Ilan M. Ruhr; Edward M. Mager; Rachael M. Heuer; Martin Grosell (Journal of Comparative Physiology B, 2021)

A Bornean peat swamp forest is a net source of carbon dioxide to the atmosphere - Angela C. I. Tang; Lulie Melling; Paul C. Stoy; Kevin K. Musin; Edward B. Aeries; Joseph W. Waili; Mariko Shimizu; Benjamin Poulter; Ryuichi Hirata (Global Change Biology, 2020)
Tropical peat forests are a globally important reservoir of carbon, but little is known about CO 2 exchange on an annual basis. We measured CO 2 exchange between the atmosphere and tropical peat swamp forest in Sarawak, Malaysia using the eddy covariance technique over 4 years from 2011 to 2014. The CO 2 fluxes varied between seasons and years. A small carbon uptake took place during the rainy season at the beginning of 2011, while a substantial net efflux of >600 g C/m 2 occurred over a 2 month period in the middle of the dry season. Conversely, the peat ecosystem was a source of carbon during both the dry and rainy seasons in subsequent years and more carbon was lost during the rainy season relative to the dry season. Our results demonstrate that the forest was a net source of CO 2 to the atmosphere during every year of measurement with annual efflux ranging from 183 to 632 g C m −2 year −1 , noting that annual flux values were sensitive to gap filling methodology. This is in contrast to the typical view of tropical peat forests which must have acted as net C sinks over time scales of centuries to millennia to create the peat deposits. Path analyses revealed that the gross primary productivity (GPP) and ecosystem respiration (RE) were primarily affected by vapour pressure deficit (VPD). Results suggest that future increases in VPD could further reduce the C sink strength and result in additional net CO 2 losses from this tropical peat swamp forest in the absence of plant acclimation to such changes in atmospheric dryness.

Treatment cost and access to care: experiences of young women diagnosed with breast cancer - Sujha Subramanian; Florence K. L. Tangka; Patrick Edwards; Madeleine Jones; Tim Flanigan; Jenya Kaganova; Kevin Smith; Cheryll C. Thomas; Nikki A. Hawkins; Juan L. Rodriguez; Gery P. Guy; Temeika Fairley (Cancer Causes & Control, 2020)

Can One-Run-Fixed-Arrhenius Kerogen Analysis Provide Comparable Organofacies Results to Detailed Palynological Analysis? A Case Study from a Prospective Mississippian Source Rock Reservoir (Bowland Shale, UK) - Sarah M. Newport; Jan A. I. Hennissen; James P. Armstrong; Kevin G. Taylor; Leo P. Newport; Edward Hough (Natural Resources Research, 2020)

Carbon Dioxide and Methane Emissions from Peat Soil in an Undrained Tropical Peat Swamp Forest - Kiwamu Ishikura; Ryuichi Hirata; Takashi Hirano; Yosuke Okimoto; Guan Xhuan Wong; Lulie Melling; Edward Baran Aeries; Frankie Kiew; Kim San Lo; Kevin Kemudang Musin; Joseph Wenceslaus Waili; Yoshiyuki Ishii (Ecosystems, 2019)

Dopaminergic drug treatment remediates exaggerated cingulate prediction error responses in obsessive-compulsive disorder - Graham K. Murray; Franziska Knolle; Karen D. Ersche; Kevin J. Craig; Sanja Abbott; Shaila S. Shabbir; Naomi A. Fineberg; John Suckling; Barbara J. Sahakian; Edward T. Bullmore; Trevor W. Robbins (Psychopharmacology, 2019)

A Euro-Mediterranean tree-ring reconstruction of the winter NAO index since 910 C.E. - Edward R. Cook; Yochanan Kushnir; Jason E. Smerdon; A. Park Williams; Kevin J. Anchukaitis; Eugene R. Wahl (Climate Dynamics, 2019)

Dynamic response of pedestrian thermal comfort under outdoor transient conditions - Kevin Ka-Lun Lau; Yuan Shi; Edward Yan-Yung Ng (International Journal of Biometeorology, 2019)

Advancing Research for the Management of Long-Lived Species: A Case Study on the Greenland Shark - Jena E. Edwards; Elizabeth Hiltz; Franziska Broell; Peter G. Bushnell; Steven E. Campana; Jørgen S. Christiansen; Brynn M. Devine; Jeffrey J. Gallant; Kevin J. Hedges; M. Aaron MacNeil; Bailey C. McMeans; Julius Nielsen; et al. (Frontiers in Marine Science, 2019)

Multi-level emulation of complex climate model responses to boundary forcing data - Giang T. Tran; Kevin I. C. Oliver; Philip B. Holden; Neil R. Edwards; András Sóbester; Peter Challenor (Climate Dynamics, 2019)

Correction to: Harden up: metal acquisition in the weaponized ovipositors of aculeate hymenoptera - Kate Baumann; Edward P. Vicenzi; Thomas Lam; Janet Douglas; Kevin Arbuckle; Bronwen Cribb; Seán G. Brady; Bryan G. Fry (Zoomorphology, 2018)

Harden up: metal acquisition in the weaponized ovipositors of aculeate hymenoptera - Kate Baumann; Edward P. Vicenzi; Thomas Lam; Janet Douglas; Kevin Arbuckle; Bronwen Cribb; Seán G. Brady; Bryan G. Fry (Zoomorphology, 2018)

Cereal cultivation as a correlate of high social status in medieval Iceland - Scott Riddell; Egill Erlendsson; Guðrún Gísladóttir; Kevin J. Edwards; Jesse Byock; Davide Zori (Vegetation History and Archaeobotany, 2018)

Evaluating and implementing social–ecological systems: A comprehensive approach to sustainable fisheries - Robert L. Stephenson; Stacey Paul; Melanie Wiber; Eric Angel; Ashleen J. Benson; Anthony Charles; Omer Chouinard; Marc Clemens; Dan Edwards; Paul Foley; Lindsay Jennings; Owen Jones; et al. (Fish and Fisheries, 2018)
Fisheries sustainability is recognized to have four pillars: ecological, economic, social (including cultural) and institutional (or governance). Although international agreements, and legislation in many jurisdictions, call for implementation of all four pillars of sustainability, the social, economic and institutional aspects (i.e., the “human dimensions”) have not been comprehensively and collectively addressed to date. This study describes a framework for comprehensive fisheries evaluation developed by the Canadian Fisheries Research Network ( CFRN ) that articulates the full spectrum of ecological, economic, social and institutional objectives required under international agreements, together with candidate performance indicators for sustainable fisheries. The CFRN framework is aimed at practical fisheries evaluation and management and has a relatively balanced distribution of elements across the four pillars of sustainability relative to 10 alternative management decision support tools and indicator scorecards, which are heavily focused on ecological and economic aspects. The CFRN framework has five immediate uses: (a) It can serve as a logic frame for defining management objectives; (b) it can be used to define alternate management options to achieve given objectives; (c) it can serve as a tool for comparing management scenarios/options in decision support frameworks; (d) it can be employed to create a report card for comprehensive fisheries management evaluation; and (e) it is a tool for practical implementation of an integrated social–ecological system approach.

BioTIME: A database of biodiversity time series for the Anthropocene - Maria Dornelas; Laura H. Antão; Faye Moyes; Amanda E. Bates; Anne E. Magurran; Dušan Adam; Asem A. Akhmetzhanova; Ward Appeltans; José Manuel Arcos; Haley Arnold; Narayanan Ayyappan; Gal Badihi; et al. (Global Ecology and Biogeography, 2018)
Motivation The BioTIME database contains raw data on species identities and abundances in ecological assemblages through time. These data enable users to calculate temporal trends in biodiversity within and amongst assemblages using a broad range of metrics. BioTIME is being developed as a community‐led open‐source database of biodiversity time series. Our goal is to accelerate and facilitate quantitative analysis of temporal patterns of biodiversity in the Anthropocene. Main types of variables included The database contains 8,777,413 species abundance records, from assemblages consistently sampled for a minimum of 2 years, which need not necessarily be consecutive. In addition, the database contains metadata relating to sampling methodology and contextual information about each record. Spatial location and grain BioTIME is a global database of 547,161 unique sampling locations spanning the marine, freshwater and terrestrial realms. Grain size varies across datasets from 0.0000000158 km 2 (158 cm 2 ) to 100 km 2 (1,000,000,000,000 cm 2 ). Time period and grain BioTIME records span from 1874 to 2016. The minimal temporal grain across all datasets in BioTIME is a year. Major taxa and level of measurement BioTIME includes data from 44,440 species across the plant and animal kingdoms, ranging from plants, plankton and terrestrial invertebrates to small and large vertebrates. Software format .csv and .SQL.

Photokinetic Drug Delivery: Near infrared (NIR) Induced Permeation Enhancement of Bevacizumab, Ranibizumab and Aflibercept through Human Sclera - Steven A. Giannos; Edward R. Kraft; Zhen-Yang Zhao; Kevin H. Merkley; Jiyang Cai (Pharmaceutical Research, 2018)

Formulation Stabilization and Disaggregation of Bevacizumab, Ranibizumab and Aflibercept in Dilute Solutions - Steven A. Giannos; Edward R. Kraft; Zhen-Yang Zhao; Kevin H. Merkley; Jiyang Cai (Pharmaceutical Research, 2018)

Complement receptor 1 gene (CR1) intragenic duplication and risk of Alzheimer’s disease - Ezgi Kucukkilic; Keeley Brookes; Imelda Barber; Tamar Guetta-Baranes; Kevin Morgan; Edward J. Hollox (Human Genetics, 2018)

“Think horizontally, act vertically”: the centenary (1916–2016) of pollen analysis and the legacy of Lennart von Post - Marie-José Gaillard; Björn E. Berglund; H. John B. Birks; Kevin J. Edwards; Felix Bittmann (Vegetation History and Archaeobotany, 2018)

Pollen, women, war and other things: reflections on the history of palynology - Kevin J. Edwards (Vegetation History and Archaeobotany, 2018)

Effects of DHA on Hippocampal Autophagy and Lysosome Function After Traumatic Brain Injury - Yan Yin; Eric Li; George Sun; Hong Q. Yan; Lesley M. Foley; Liwia A. Andrzejczuk; Insiya Y. Attarwala; T. Kevin Hitchens; Kirill Kiselyov; C. Edward Dixon; Dandan Sun (Molecular Neurobiology, 2018)

How palynology could have been paepalology: the naming of a discipline - Kevin J. Edwards; Heather S. Pardoe (Palynology, 2018)

Asynchrony among local communities stabilises ecosystem function of metacommunities - Kevin R. Wilcox; Andrew T. Tredennick; Sally E. Koerner; Emily Grman; Lauren M. Hallett; Meghan L. Avolio; Kimberly J. La Pierre; Gregory R. Houseman; Forest Isbell; David Samuel Johnson; Juha M. Alatalo; Andrew H. Baldwin; et al. (Ecology Letters, 2017)
Temporal stability of ecosystem functioning increases the predictability and reliability of ecosystem services, and understanding the drivers of stability across spatial scales is important for land management and policy decisions. We used species‐level abundance data from 62 plant communities across five continents to assess mechanisms of temporal stability across spatial scales. We assessed how asynchrony (i.e. different units responding dissimilarly through time) of species and local communities stabilised metacommunity ecosystem function. Asynchrony of species increased stability of local communities, and asynchrony among local communities enhanced metacommunity stability by a wide range of magnitudes (1–315%); this range was positively correlated with the size of the metacommunity. Additionally, asynchronous responses among local communities were linked with species’ populations fluctuating asynchronously across space, perhaps stemming from physical and/or competitive differences among local communities. Accordingly, we suggest spatial heterogeneity should be a major focus for maintaining the stability of ecosystem services at larger spatial scales.

Political transition and emergent forest‐conservation issues in Myanmar - Graham W. Prescott; William J. Sutherland; Daniel Aguirre; Matthew Baird; Vicky Bowman; Jake Brunner; Grant M. Connette; Martin Cosier; David Dapice; Jose Don T. De Alban; Alex Diment; Julia Fogerite; et al. (Conservation Biology, 2017)
Political and economic transitions have had substantial impacts on forest conservation. Where transitions are underway or anticipated, historical precedent and methods for systematically assessing future trends should be used to anticipate likely threats to forest conservation and design appropriate and prescient policy measures to counteract them. Myanmar is transitioning from an authoritarian, centralized state with a highly regulated economy to a more decentralized and economically liberal democracy and is working to end a long‐running civil war. With these transitions in mind, we used a horizon‐scanning approach to assess the 40 emerging issues most affecting Myanmar's forests, including internal conflict, land‐tenure insecurity, large‐scale agricultural development, demise of state timber enterprises, shortfalls in government revenue and capacity, and opening of new deforestation frontiers with new roads, mines, and hydroelectric dams. Averting these threats will require, for example, overhauling governance models, building capacity, improving infrastructure‐ and energy‐project planning, and reforming land‐tenure and environmental‐protection laws. Although challenges to conservation in Myanmar are daunting, the political transition offers an opportunity for conservationists and researchers to help shape a future that enhances Myanmar's social, economic, and environmental potential while learning and applying lessons from other countries. Our approach and results are relevant to other countries undergoing similar transitions.

Speciation and potential long-term behaviour of chromium in urban sediment particulates - Patrick Byrne; Kevin G. Taylor; Karen A. Hudson-Edwards; Judith E. S. Barrett (Journal of Soils and Sediments, 2017)

Characterizing prolonged heat effects on mortality in a sub-tropical high-density city, Hong Kong - Hung Chak Ho; Kevin Ka-Lun Lau; Chao Ren; Edward Ng (International Journal of Biometeorology, 2017)

Evaluation of Nitrogen Concentration in Final Effluent of Advanced Nitrogen-Removal Onsite Wastewater Treatment Systems (OWTS) - Brittany V. Lancellotti; George W. Loomis; Kevin P. Hoyt; Edward Avizinis; Jose A. Amador (Water, Air, & Soil Pollution, 2017)

Asymmetric responses of primary productivity to precipitation extremes: A synthesis of grassland precipitation manipulation experiments - Kevin R. Wilcox; Zheng Shi; Laureano A. Gherardi; Nathan P. Lemoine; Sally E. Koerner; David L. Hoover; Edward Bork; Kerry M. Byrne; James Cahill; Scott L. Collins; Sarah Evans; Anna K. Gilgen; et al. (Global Change Biology, 2017)
Climatic changes are altering Earth's hydrological cycle, resulting in altered precipitation amounts, increased interannual variability of precipitation, and more frequent extreme precipitation events. These trends will likely continue into the future, having substantial impacts on net primary productivity ( NPP ) and associated ecosystem services such as food production and carbon sequestration. Frequently, experimental manipulations of precipitation have linked altered precipitation regimes to changes in NPP . Yet, findings have been diverse and substantial uncertainty still surrounds generalities describing patterns of ecosystem sensitivity to altered precipitation. Additionally, we do not know whether previously observed correlations between NPP and precipitation remain accurate when precipitation changes become extreme. We synthesized results from 83 case studies of experimental precipitation manipulations in grasslands worldwide. We used meta‐analytical techniques to search for generalities and asymmetries of aboveground NPP ( ANPP ) and belowground NPP ( BNPP ) responses to both the direction and magnitude of precipitation change. Sensitivity (i.e., productivity response standardized by the amount of precipitation change) of BNPP was similar under precipitation additions and reductions, but ANPP was more sensitive to precipitation additions than reductions; this was especially evident in drier ecosystems. Additionally, overall relationships between the magnitude of productivity responses and the magnitude of precipitation change were saturating in form. The saturating form of this relationship was likely driven by ANPP responses to very extreme precipitation increases, although there were limited studies imposing extreme precipitation change, and there was considerable variation among experiments. This highlights the importance of incorporating gradients of manipulations, ranging from extreme drought to extreme precipitation increases into future climate change experiments. Additionally, policy and land management decisions related to global change scenarios should consider how ANPP and BNPP responses may differ, and that ecosystem responses to extreme events might not be predicted from relationships found under moderate environmental changes.

Effects of nalfurafine on the reinforcing, thermal antinociceptive, and respiratory-depressant effects of oxycodone: modeling an abuse-deterrent opioid analgesic in rats - E. Andrew Townsend; Jennifer E. Naylor; S. Stevens Negus; Shelley R. Edwards; Hina N. Qureshi; Hunter W. McLendon; Christopher R. McCurdy; Coco N. Kapanda; Jussara M. do Carmo; Fernanda S. da Silva; John E. Hall; Kenneth J. Sufka; et al. (Psychopharmacology, 2017)

High-resolution palynology reveals the land use history of a Sami renvall in northern Sweden - Ilse M. Kamerling; J. Edward Schofield; Kevin J. Edwards; Kjell-Åke Aronsson (Vegetation History and Archaeobotany, 2017)

History of hypertension, heart disease, and diabetes and ovarian cancer patient survival: evidence from the ovarian cancer association consortium - Albina N. Minlikeeva; Jo L. Freudenheim; Rikki A. Cannioto; J. Brian Szender; Kevin H. Eng; Francesmary Modugno; Roberta B. Ness; Michael J. LaMonte; Grace Friel; Brahm H. Segal; Kunle Odunsi; Paul Mayor; et al. (Cancer Causes & Control, 2017)

Estimating the ecological, economic and social impacts of ocean acidification and warming on UK fisheries - Jose A Fernandes; Eleni Papathanasopoulou; Caroline Hattam; Ana M Queirós; William W W L Cheung; Andrew Yool; Yuri Artioli; Edward C Pope; Kevin J Flynn; Gorka Merino; Piero Calosi; Nicola Beaumont; et al. (Fish and Fisheries, 2017)
Assessments of the combined ecological impacts of ocean acidification and warming ( OAW ) and their social and economic consequences can help develop adaptive and responsive management strategies in the most sensitive regions. Here, available observational and experimental data, theoretical, and modelling approaches are combined to project and quantify potential effects of OAW on the future fisheries catches and resulting revenues and employment in the UK under different CO 2 emission scenarios. Across all scenarios, based on the limited available experimental results considered, the bivalve species investigated were more affected by OAW than the fish species considered, compared with ocean warming alone. Projected standing stock biomasses decrease between 10 and 60%. These impacts translate into an overall fish and shellfish catch decrease of between 10 and 30% by 2020 across all areas except for the Scotland >10 m fleet. This latter fleet shows average positive impacts until 2050, declining afterwards. The main driver of the projected decreases is temperature rise (0.5–3.3 °C), which exacerbate the impact of decreases in primary production (10–30%) in UK fishing waters. The inclusion of the effect of ocean acidification on the carbon uptake of primary producers had very little impact on the projections of potential fish and shellfish catches ( 10 m fleet by the end of the century in all countries. Overall, losses in revenue are estimated to range between 1 and 21% in the short term (2020–50) with England and Scotland being the most negatively impacted in absolute terms, and Wales and North Ireland in relative terms. Losses in total employment (fisheries and associated industries) may reach approximately 3–20% during 2020–50 with the >10 m fleet and associated industries bearing the majority of the losses.

Continued feeding on Diporeia by deepwater sculpin in Lake Huron - Patricia A. Thompson; Edward F. Roseman; Kevin M. Keeler; Timothy P. O’Brien; Dustin A. Bowser (Environmental Biology of Fishes, 2017)

Ecosystem responses to climate change at a Low Arctic and a High Arctic long-term research site - John E. Hobbie; Gaius R. Shaver; Edward B. Rastetter; Jessica E. Cherry; Scott J. Goetz; Kevin C. Guay; William A. Gould; George W. Kling (Ambio, 2017)

Losing Legacies, Ecological Release, and Transient Responses: Key Challenges for the Future of Northern Ecosystem Science - Merritt R. Turetsky; Jennifer L. Baltzer; Jill F. Johnstone; Michelle C. Mack; Kevin McCann; Edward A. G. Schuur (Ecosystems, 2017)

Accuracy of Rapid Tests Used for Analysis of Advanced Onsite Wastewater Treatment System Effluent - Brittany V. Lancellotti; Robert J. Bercaw; George W. Loomis; Kevin P. Hoyt; Edward J. Avizinis; Jose A. Amador (Water, Air, & Soil Pollution, 2016)

The biogeographical status of Alnus crispa (Ait.) Pursch in sub-Arctic southern Greenland: Do pollen records indicate local populations during the past 1500 years? - Paul M. Ledger; Kevin J. Edwards; J. Edward Schofield (Polar Biology, 2016)

Development of Tablet Formulation of Amorphous Solid Dispersions Prepared by Hot Melt Extrusion Using Quality by Design Approach - Anjali Agrawal; Mayur Dudhedia; Weibin Deng; Kevin Shepard; Li Zhong; Edward Povilaitis; Ewa Zimny (AAPS PharmSciTech, 2016)

Evidence of the St. Clair-Detroit River System as a dispersal corridor and nursery habitat for transient larval burbot - Darrin E. McCullough; Edward F. Roseman; Kevin M. Keeler; Robin L. DeBruyne; Jeremy J. Pritt; Patricia A. Thompson; Stacey Ireland; Jason E. Ross; Dustin Bowser; Robert D. Hunter; Dana Castle; Jason L. Fischer; et al. (Hydrobiologia, 2015)

Horizon scanning for invasive alien species with the potential to threaten biodiversity in Great Britain - Helen E. Roy; Jodey Peyton; David C. Aldridge; Tristan Bantock; Tim M. Blackburn; Robert Britton; Paul Clark; Elizabeth Cook; Katharina Dehnen‐Schmutz; Trevor Dines; Michael Dobson; François Edwards; et al. (Global Change Biology, 2014)
Invasive alien species ( IAS ) are considered one of the greatest threats to biodiversity, particularly through their interactions with other drivers of change. Horizon scanning, the systematic examination of future potential threats and opportunities, leading to prioritization of IAS threats is seen as an essential component of IAS management. Our aim was to consider IAS that were likely to impact on native biodiversity but were not yet established in the wild in Great Britain. To achieve this, we developed an approach which coupled consensus methods (which have previously been used for collaboratively identifying priorities in other contexts) with rapid risk assessment. The process involved two distinct phases: Preliminary consultation with experts within five groups (plants, terrestrial invertebrates, freshwater invertebrates, vertebrates and marine species) to derive ranked lists of potential IAS. Consensus‐building across expert groups to compile and rank the entire list of potential IAS. Five hundred and ninety‐one species not native to Great Britain were considered. Ninety‐three of these species were agreed to constitute at least a medium risk (based on score and consensus) with respect to them arriving, establishing and posing a threat to native biodiversity. The quagga mussel, Dreissena rostriformis bugensis , received maximum scores for risk of arrival, establishment and impact; following discussions the unanimous consensus was to rank it in the top position. A further 29 species were considered to constitute a high risk and were grouped according to their ranked risk. The remaining 63 species were considered as medium risk, and included in an unranked long list. The information collated through this novel extension of the consensus method for horizon scanning provides evidence for underpinning and prioritizing management both for the species and, perhaps more importantly, their pathways of arrival. Although our study focused on Great Britain, we suggest that the methods adopted are applicable globally.

Early Diagnosis of Orthopedic Implant Failure Using Macromolecular Imaging Agents - Ke Ren; Anand Dusad; Yijia Zhang; P. Edward Purdue; Edward V. Fehringer; Kevin L. Garvin; Steven R. Goldring; Dong Wang (Pharmaceutical Research, 2014)

Controls on water balance of shallow thermokarst lakes and their relations with catchment characteristics: a multi‐year, landscape‐scale assessment based on water isotope tracers and remote sensing in Old Crow Flats, Yukon (Canada) - Kevin W. Turner; Brent B. Wolfe; Thomas W. D. Edwards; Trevor C. Lantz; Roland I. Hall; Guillaume Larocque (Global Change Biology, 2014)
Many northern lake‐rich regions are undergoing pronounced hydrological change, yet inadequate knowledge of the drivers of these landscape‐scale responses hampers our ability to predict future conditions. We address this challenge in the thermokarst landscape of Old Crow Flats ( OCF ) using a combination of remote sensing imagery and monitoring of stable isotope compositions of lake waters over three thaw seasons (2007–2009). Quantitative analysis confirmed that the hydrological behavior of lakes is strongly influenced by catchment vegetation and physiography. Catchments of snowmelt‐dominated lakes, typically located in southern peripheral areas of OCF , encompass high proportions of woodland/forest and tall shrub vegetation (mean percent land cover = ca. 60%). These land cover types effectively capture snow and generate abundant snowmelt runoff that offsets lake water evaporation. Rainfall‐dominated lakes that are not strongly influenced by evaporation are typically located in eastern and northern OCF where their catchments have higher proportions of dwarf shrub/herbaceous and sparse vegetation (ca. 45%), as well as surface water (ca. 20%). Evaporation‐dominated lakes, are located in the OCF interior where their catchments are distinguished by substantially higher lake area to catchment area ratios ( LA / CA = ca. 29%) compared to low evaporation‐influenced rainfall‐dominated (ca. 10%) and snowmelt‐dominated (ca. 4%) lakes. Lakes whose catchments contain >75% combined dwarf shrub/herbaceous vegetation and surface water are most susceptible to evaporative lake‐level drawdown, especially following periods of low precipitation. Findings indicate that multiple hydrological trajectories are probable in response to climate‐driven changes in precipitation amount and seasonality, vegetation composition, and thermokarst processes. These will likely include a shift to greater snowmelt influence in catchments experiencing expansion of tall shrubs, greater influence from evaporation in catchments having higher proportions of surface water, and an increase in the rate of thermokarst lake expansion and probability of drainage. Local observations suggest that some of these changes are already underway.

Tree-ring reconstructed summer temperature anomalies for temperate East Asia since 800 C.E. - Edward R. Cook; Paul J. Krusic; Kevin J. Anchukaitis; Brendan M. Buckley; Takeshi Nakatsuka; Masaki Sano (Climate Dynamics, 2013)

Characterization of STR/microsatellite primers for the Gila monster, Heloderma suspectum screened from paired-end Illumina shotgun sequencing - Michael R. Hess; Taylor Edwards; David A. Edmunds; Kevin E. Bonine (Conservation Genetics Resources, 2013)

Erratum to: The European Modern Pollen Database (EMPD) project - Basil A. S. Davis; Marco Zanon; Pamella Collins; Achille Mauri; Johan Bakker; Doris Barboni; Alexandra Barthelmes; Celia Beaudouin; H. John B. Birks; Anne E. Bjune; Elissaveta Bozilova; Richard H. W. Bradshaw; et al. (Vegetation History and Archaeobotany, 2013)

The European Modern Pollen Database (EMPD) project - Basil A. S. Davis; Marco Zanon; Pamella Collins; Achille Mauri; Johan Bakker; Doris Barboni; Alexandra Barthelmes; Celia Beaudouin; Anne E. Bjune; Elissaveta Bozilova; Richard H. W. Bradshaw; Barbara A. Brayshay; et al. (Vegetation History and Archaeobotany, 2013)

Erratum to: Phreatophytes under stress: transpiration and stomatal conductance of saltcedar (Tamarix spp.) in a high-salinity environment - Edward P. Glenn; Pamela L. Nagler; Kiyomi Morino; Kevin R. Hultine (Plant and Soil, 2013)

Phreatophytes under stress: transpiration and stomatal conductance of saltcedar (Tamarix spp.) in a high-salinity environment - Edward P. Glenn; Pamela L. Nagler; Kiyomi Morino; Kevin R. Hultine (Plant and Soil, 2013)

Recent advances in 2D and 3D in vitro systems using primary hepatocytes, alternative hepatocyte sources and non-parenchymal liver cells and their use in investigating mechanisms of hepatotoxicity, cell signaling and ADME - Patricio Godoy; Nicola J. Hewitt; Ute Albrecht; Melvin E. Andersen; Nariman Ansari; Sudin Bhattacharya; Johannes Georg Bode; Jennifer Bolleyn; Christoph Borner; Jan Böttger; Albert Braeuning; Robert A. Budinsky; et al. (Archives of Toxicology, 2013)

Isolation and characterization of polymorphic microsatellite loci from the golden mouse (Ochrotomys nuttalli) - Edward J. Heist; Jill C. Devine; Jeffrey W. Gersch; Kevin M. Kingsland; Bryan M. Musungu; Amanda J. Warner; Sydney K. Youngs; Elliott A. Zieman (Conservation Genetics Resources, 2013)

Palynology supports ‘ O ld N orse’ introductions to the flora of G reenland - J. Edward Schofield; Kevin J. Edwards; Egill Erlendsson; Paul M. Ledger (Journal of Biogeography, 2013)
Aim This paper integrates pollen‐analytical data from sites across southern G reenland to revisit the debate regarding which plants may have been introduced during the N orse colonization or landnám c . ad 985. Location Palynological data are drawn from 14 sites (lakes and mires) located within the former E astern S ettlement of N orse G reenland ( c . 60.9° N, 45.5° W). Methods Maps are presented displaying palynological data for three taxa ( R umex acetosella , P olygonum aviculare and A chillea millefolium ), which earlier scholars have argued are ‘Old Norse’ anthropochores. The maps display pollen frequencies at regular ( c . 100‐year) intervals across a period ( ad 800–1500) encompassing N orse settlement. Results Maps for c . ad 800 and 900 (prior to N orse arrival) display the taxa as locally absent, with the appearance and expansion of their pollen at multiple sites from c . ad 1000 ( landnám ) providing support for the assumption that each taxon arrived with the first settlers. A general and widespread decline in pollen frequencies for these ‘Old Norse’ elements on the c. ad 1500 map (following N orse abandonment) demonstrates a close connection between these plants and a cultural landscape that was shaped and maintained predominantly via animal husbandry. Main conclusions Patterns emerging from this exercise may initiate wider debates related to the pattern and character of the N orse colonization of G reenland. It is suggested that differences in the function or role of farm sites could have led to the creation of greater areas of favourable habitat for ‘ O ld N orse’ flora in some locations relative to others, and that uneven patterns of colonization and the spread of ‘ O ld N orse’ plants might be explained if their introduction – presumably from Iceland – first occurred at only a few locations.

Investigation of proposed Norse irrigation channels and dams at Garðar/Igaliku, Greenland - Kevin J. Edwards; J. Edward Schofield (Water History, 2013)

Volcanic impacts on the Holocene vegetation history of Britain and Ireland? A review and meta-analysis of the pollen evidence - Richard J. Payne; Kevin J. Edwards; Jeff J. Blackford (Vegetation History and Archaeobotany, 2013)

Links between Indo-Pacific climate variability and drought in the Monsoon Asia Drought Atlas - Caroline C. Ummenhofer; Rosanne D. D’Arrigo; Kevin J. Anchukaitis; Brendan M. Buckley; Edward R. Cook (Climate Dynamics, 2013)

Polymorphisms in genes related to one-carbon metabolism are not related to pancreatic cancer in PanScan and PanC4 - Max Leenders; Samsiddhi Bhattacharjee; Paolo Vineis; Victoria Stevens; H. Bas Bueno-de-Mesquita; Xiao-Ou Shu; Laufey Amundadottir; Myron Gross; Geoffrey S. Tobias; Jean Wactawski-Wende; Alan A. Arslan; Eric J. Duell; et al. (Cancer Causes & Control, 2013)

Effects of cadmium on the sub-cellular localization of β-catenin and β-catenin-regulated gene expression in NRK-52E cells - Joshua R. Edwards; Kevin Kolman; Peter C. Lamar; Nalini Chandar; Michael J. Fay; Walter C. Prozialeck (BioMetals, 2013)

Diabetes and risk of pancreatic cancer: a pooled analysis from the pancreatic cancer cohort consortium - Joanne W. Elena; Emily Steplowski; Kai Yu; Patricia Hartge; Geoffrey S. Tobias; Michelle J. Brotzman; Stephen J. Chanock; Rachael Z. Stolzenberg-Solomon; Alan A. Arslan; H. Bas Bueno-de-Mesquita; Kathy Helzlsouer; Eric J. Jacobs; et al. (Cancer Causes & Control, 2013)

The mechanism of gall induction makes galls red - Edward F. Connor; Linnea Bartlett; Sean O’Toole; Steven Byrd; Kevin Biskar; Jessica Orozco (Arthropod-Plant Interactions, 2012)

Oxygen minimum zones harbour novel viral communities with low diversity - Noriko Cassman; Alejandra Prieto‐Davó; Kevin Walsh; Genivaldo G. Z. Silva; Florent Angly; Sajia Akhter; Katie Barott; Julia Busch; Tracey McDole; J. Matthew Haggerty; Dana Willner; Gadiel Alarcón; et al. (Environmental Microbiology, 2012)
Summary Oxygen minimum zones ( OMZs ) are oceanographic features that affect ocean productivity and biodiversity, and contribute to ocean nitrogen loss and greenhouse gas emissions. Here we describe the viral communities associated with the E astern T ropical S outh P acific ( ETSP ) OMZ off I quique, C hile for the first time through abundance estimates and viral metagenomic analysis. The viral‐to‐microbial ratio ( VMR ) in the ETSP OMZ fluctuated in the oxycline and declined in the anoxic core to below one on several occasions. The number of viral genotypes (unique genomes as defined by sequence assembly) ranged from 2040 at the surface to 98 in the oxycline, which is the lowest viral diversity recorded to date in the ocean. Within the ETSP OMZ viromes, only 4.95% of genotypes were shared between surface and anoxic core viromes using reciprocal BLASTn sequence comparison. ETSP virome comparison with surface marine viromes ( S argasso S ea, G ulf of M exico, K ingman R eef, C hesapeake B ay) revealed a dissimilarity of ETSP OMZ viruses to those from other oceanic regions. From the 1.4 million non‐redundant DNA sequences sampled within the altered oxygen conditions of the ETSP OMZ , more than 97.8% were novel. Of the average 3.2% of sequences that showed similarity to the SEED non‐redundant database, phage sequences dominated the surface viromes, eukaryotic virus sequences dominated the oxycline viromes, and phage sequences dominated the anoxic core viromes. The viral community of the ETSP OMZ was characterized by fluctuations in abundance, taxa and diversity across the oxygen gradient. The ecological significance of these changes was difficult to predict; however, it appears that the reduction in oxygen coincides with an increased shedding of eukaryotic viruses in the oxycline, and a shift to unique viral genotypes in the anoxic core.

Effects of exposure to amphetamine derivatives on passive avoidance performance and the central levels of monoamines and their metabolites in mice: Correlations between behavior and neurochemistry - Kevin Sean Murnane; Shane Alan Perrine; Brendan James Finton; Matthew Peter Galloway; Leonard Lee Howell; William Edward Fantegrossi (Psychopharmacology, 2012)

Advances in winter pulse pathology research in Australia - Moin U. Salam; Jennifer A. Davidson; Geoff J. Thomas; Rebecca Ford; Roger A. C. Jones; Kurt D. Lindbeck; William J. MacLeod; Rohan B. E. Kimber; Jean Galloway; Nitin Mantri; Joop A. G. van Leur; Brenda A. Coutts; et al. (Australasian Plant Pathology, 2011)

Problematic but promising ponds? Palaeoenvironmental evidence from the Norse Eastern Settlement of Greenland - Kevin J. Edwards; J. Edward Schofield; Jason R. Kirby; Gordon T. Cook (Journal of Quaternary Science, 2011)
Pollen‐ and related proxy‐based studies of human–environment interactions during the Norse and later periods within Greenland have primarily involved the investigation of peat, lake and soil deposits, all of which have taphonomic and sampling problems. Many small ponds exist, but they seem to have been relatively ignored in investigations of palaeoecologically based environmental history. To evaluate their usefulness for studies of ecologically related cultural history, especially where sites are in intimate association with the archaeology, a pond in the Norse Eastern Settlement has been examined to investigate three principal questions: (i) Does such a site contain a useful record of environmental history? (ii) Does it offer a record of sufficient resolution and sensitivity for the study of anthropogenic landscape impacts? (iii) Are there any apparent drawbacks to these sequences? Using data obtained from palynological, diatom, sedimentological and radiocarbon analyses, it is concluded that environmental data for each proxy – aside from 14 C dating – are clearly capable of being explained in a reasonably straightforward and compatible manner and fulfil the hopes for the sampling medium. Copyright © 2011 John Wiley & Sons, Ltd.

Forced and unforced variability of twentieth century North American droughts and pluvials - Benjamin I. Cook; Edward R. Cook; Kevin J. Anchukaitis; Richard Seager; Ron L. Miller (Climate Dynamics, 2011)

Repurposing climate reconstructions for drought prediction in Southeast Asia - Andrew R. Bell; Benjamin I. Cook; Kevin J. Anchukaitis; Brendan M. Buckley; Edward R. Cook (Climatic Change, 2011)

Grazing impacts and woodland management in Eriksfjord: Betula, coprophilous fungi and the Norse settlement of Greenland - J. Edward Schofield; Kevin J. Edwards (Vegetation History and Archaeobotany, 2011)

CyberShake: A Physics-Based Seismic Hazard Model for Southern California - Robert Graves; Thomas H. Jordan; Scott Callaghan; Ewa Deelman; Edward Field; Gideon Juve; Carl Kesselman; Philip Maechling; Gaurang Mehta; Kevin Milner; David Okaya; Patrick Small; et al. (Pure and Applied Geophysics, 2011)

Pulmonary Immunization of Guinea Pigs with Diphtheria CRM-197 Antigen as Nanoparticle Aggregate Dry Powders Enhance Local and Systemic Immune Responses - Pavan Muttil; Brian Pulliam; Lucila Garcia-Contreras; John Kevin Fallon; Chenchen Wang; Anthony James Hickey; David A. Edwards (The AAPS Journal, 2010)

Impaired visuospatial associative memory and attention in obsessive compulsive disorder but no evidence for differential dopaminergic modulation - Sharon Morein-Zamir; Kevin J. Craig; Karen D. Ersche; Sanja Abbott; Ulrich Muller; Naomi A. Fineberg; Edward T. Bullmore; Barbara J. Sahakian; Trevor W. Robbins (Psychopharmacology, 2010)

Immunization of Guinea Pigs with Novel Hepatitis B Antigen as Nanoparticle Aggregate Powders Administered by the Pulmonary Route - Pavan Muttil; Cecilia Prego; Lucila Garcia-Contreras; Brian Pulliam; John Kevin Fallon; Chenchen Wang; Anthony James Hickey; David Edwards (The AAPS Journal, 2010)

Alcohol intake and pancreatic cancer: a pooled analysis from the pancreatic cancer cohort consortium (PanScan) - Dominique S. Michaud; Alina Vrieling; Li Jiao; Julie B. Mendelsohn; Emily Steplowski; Shannon M. Lynch; Jean Wactawski-Wende; Alan A. Arslan; H. Bas Bueno-de-Mesquita; Charles S. Fuchs; Myron Gross; Kathy Helzlsouer; et al. (Cancer Causes & Control, 2010)

Using photographic image analysis to assess ground cover: a case study of forest road cutbanks - Kevin C. Bold; Frederica Wood; Pamela J. Edwards; Karl W. J. Williard; Jon E. Schoonover (Environmental Monitoring and Assessment, 2010)

The interaction between thymine DNA glycosylase and nuclear receptor coactivator 3 is required for the transcriptional activation of nuclear hormone receptors - Shirley Chiang; Tanya Burch; Gary Van Domselaar; Kevin Dick; Alina Radziwon; Craig Brusnyk; Megan Rae Edwards; Jessica Piper; Todd Cutts; Jingxin Cao; Xuguang Li; Runtao He (Molecular and Cellular Biochemistry, 2010)

Lake sediment evidence for late Holocene climate change and landscape erosion in western Iceland - Freddy J. Gathorne-Hardy; Egill Erlendsson; Peter G. Langdon; Kevin J. Edwards (Journal of Paleolimnology, 2009)

Near real‐time, autonomous detection of marine bacterioplankton on a coastal mooring in Monterey Bay, California, using rRNA‐targeted DNA probes - Christina M. Preston; Roman Marin; Scott D. Jensen; Jason Feldman; James M. Birch; Eugene I. Massion; Edward F. DeLong; Marcelino Suzuki; Kevin Wheeler; Christopher A. Scholin (Environmental Microbiology, 2009)
Summary A sandwich hybridization assay (SHA) was developed to detect 16S rRNAs indicative of phylogenetically distinct groups of marine bacterioplankton in a 96‐well plate format as well as low‐density arrays printed on a membrane support. The arrays were used in a field‐deployable instrument, the Environmental Sample Processor (ESP). The SHA employs a chaotropic buffer for both cell homogenization and hybridization, thus target sequences are captured directly from crude homogenates. Capture probes for seven of nine different bacterioplankton clades examined reacted specifically when challenged with target and non‐target 16S rRNAs derived from in vitro transcribed 16S rRNA genes cloned from natural samples. Detection limits were between 0.10–1.98 and 4.43– 12.54 fmole ml −1 homogenate for the 96‐well plate and array SHA respectively. Arrays printed with five of the bacterioplankton‐specific capture probes were deployed on the ESP in Monterey Bay, CA, twice in 2006 for a total of 25 days and also utilized in a laboratory time series study. Groups detected included marine alphaproteobacteria, SAR11, marine cyanobacteria, marine group I crenarchaea, and marine group II euryarchaea. To our knowledge this represents the first report of remote in situ DNA probe‐based detection of marine bacterioplankton.

Selection and application of a rainbow trout toxicity testing procedure for screening Sacramento River Watershed, California samples - Jeffrey L. Miller; Michael J. Miller; Victor de Vlaming; Karen Larsen; Edward Smith; Kevin Reece (Environmental Monitoring and Assessment, 2009)

Barley (Hordeum vulgare L.) inositol monophosphatase: gene structure and enzyme characteristics - Jianming Fu; Kevin Peterson; Mary Guttieri; Edward Souza; Victor Raboy (Plant Molecular Biology, 2008)

ORIGINAL ARTICLE: Human impact on an island ecosystem: pollen data from Sandoy, Faroe Islands - Ian T. Lawson; Kevin J. Edwards; Mike J. Church; Anthony J. Newton; Gordon T. Cook; Freddy J. Gathorne‐Hardy; Andrew J. Dugmore (Journal of Biogeography, 2008)
Aim To investigate the form and dynamics of ecosystems on an isolated island in the North Atlantic before human settlement in the first millennium ad , and the effects of human activities thereafter. Location The island of Sandoy, Faroes (61°50′ N, 6°45′ W). Methods Two sequences of lake sediments and one of peat were studied using pollen analysis and sedimentological techniques. Age models were constructed on the basis of radiocarbon dating and, in one case, tephrochronology. The data were analysed statistically and compared with existing data from the region. Results The pollen data indicate that early Holocene vegetation consisted of fell‐field communities probably growing on raw, skeletal soils. These communities gave way to grass‐ and sedge‐dominated communities, which in turn were largely replaced by dwarf shrub‐dominated blanket mire communities well before the first arrival of humans. There is evidence for episodic soil erosion, particularly in the uplands. Changes in the records attributable to human impact are minor in comparison with many other situations in the North Atlantic margins, and with certain published sequences from elsewhere in the Faroes. They include: (1) the appearance of cereal pollen and charcoal, (2) an expansion of ruderal taxa, (3) a decline in certain taxa, notably Juniperus communis and Filipendula ulmaria , and (4) a renewed increase in rates of upland soil erosion. The reliability of palaeoecological inferences drawn from these sites, and more generally from sites in similar unforested situations, is discussed. Main conclusions The subdued amplitude of palynological and sedimentological responses to settlement at these sites can be explained partly in terms of their location and partly in terms of the sensitivity of different parts of the ecosystem to human activities. This study is important in establishing that the imposition of people on the pristine environment of Sandoy, while far from negligible, especially in the immediate vicinity of early farms and at high altitudes, had relatively little ecological impact in many parts of the landscape.

External mechanical compression reduces regional arterial stiffness - Kevin S. Heffernan; David G. Edwards; Lindy Rossow; Sae Young Jae; Bo Fernhall (European Journal of Applied Physiology, 2007)

The use of incidence-based species richness estimators, species accumulation curves and similarity measures to appraise ethnobotanical inventories from South Africa - Vivienne L. Williams; Edward T. F. Witkowski; Kevin Balkwill (Biodiversity and Conservation, 2007)

Modern pollen–vegetation relationships in subarctic southern Greenland and the interpretation of fossil pollen data from the Norse landnám - J. Edward Schofield; Kevin J. Edwards; J. Andy McMullen (Journal of Biogeography, 2007)
Aim The objective of this paper is to explore the relationships that exist between vegetation and modern pollen rain in the open, largely treeless landscape of subarctic Greenland. The implications of these results for the interpretation of fossil pollen assemblages from the time of the Norse landnám are then examined. Location The study area is the sheep farming district of Qassiarsuk in the subarctic, subcontinental vegetational and climatic zone of southern Greenland (61° N, 45° W). Between c. ad 1000–1500 this region was contained within the Norse Eastern Settlement. Methods Detrended Correspondence Analysis (DCA) of harmonized plant–pollen data sets is used to compare plant cover in 64 vegetation quadrats with pollen assemblages obtained from moss polsters at matching locations. Presence/absence data are also used to calculate indices of association, over‐ and under‐representation for pollen types. Results Good correspondence between paired vegetation–pollen samples occurs in many cases, particularly in locations where Salix glauca – Betula glandulosa dwarf shrub heath is dominant, and across herbaceous field boundaries and meadows. Pollen samples are found to be poor at reflecting actual ground cover where ericales or Juniperus communis are the locally dominant shrubs. Dominant or ubiquitous taxa within this landscape ( Betula , Salix and Poaceae) are found to be over‐represented in pollen assemblages, as are several of the ‘weeds’ generally accepted as introduced by the Norse settlers. Main conclusions Due to their over‐representation in the pollen rain, many of the Norse apophytes and introductions (e.g. Rumex acetosa and R. acetosella ) traditionally used to infer human activity in Greenland should be particularly sensitive indicators for landnám , allowing early detection of Norse activity in fossil assemblages. Pteridophyte spores are found to be disassociated with the ground cover of ferns and clubmosses, but are over‐represented in pollen assemblages, indicating extra‐local or regional sources and long residence times in soil/sediment profiles for these microfossils. A pollen record for Hordeum ‐type registered in close proximity to a field containing barley suggests that summer temperatures under the current climatic regime are, at least on occasion, sufficient to allow flowering.

Separating climatic and possible human impacts in the early Holocene: biotic response around the time of the 8200 cal. yr BP event - Kevin J. Edwards; Peter G. Langdon; Heather Sugden (Journal of Quaternary Science, 2007)
The early Holocene is characterised by rapid climate change events, which in the North Atlantic region are often associated with changes in thermohaline circulation. Superimposed on this in northwest Europe is localised evidence for human impact on the landscape, although separating climatic and anthropogenic mechanisms for environmental change is often difficult. Biotic and sedimentological evidence from a lacustrine sequence from the Inner Hebrides, Scotland, shows a considerable reduction in inferred local woodland centred upon 8250 cal. yr BP. These data correlate precisely with a distinctive rise in the charcoal:pollen ratio and hence suggest a possible Mesolithic human impact upon the vegetation around this time. A quantitative temperature reconstruction from chironomid analyses from the same sequence, supported by sedimentological data, indicates that the fall in arboreal pollen taxa occurred as climate warmed significantly during the early Holocene. This warming was followed by a significant cold event, with mean July temperatures reduced by 2°C, that lasted for at least 320 years ca. 7790–7470 cal. yr BP. Woodland recovered during this phase suggesting that the vegetation during the 8250 cal. yr BP interval was likely to have been responding to human activity, and not climate, and hence it is possible at specific sites to separate the influence of these key drivers of environmental change. Copyright © 2006 John Wiley & Sons, Ltd.

Development of a real-time three-dimensional spinal motion measurement system for clinical practice - Christina Goodvin; Edward J. Park; Kevin Huang; Kelly Sakaki (Medical & Biological Engineering & Computing, 2006)

Comparative phylogeography of eastern chipmunks and white‐footed mice in relation to the individualistic nature of species - KEVIN C. ROWE; EDWARD J. HESKE; KEN N. PAIGE (Molecular Ecology, 2006)
Palaeoecological studies have demonstrated that ecological communities as a whole did not remain stable throughout the climatic fluctuations of the Quaternary. The result is that long‐term associations of species cannot be inferred by contemporary associations in ecological communities. Therefore, the evolutionary significance of any contemporary ecological interactions among species and of the biotic community within which species have evolved also cannot be assumed from contemporary conditions. Comparative phylogeographic data provide a method to identify species within ecological communities that have shared biogeographic histories. We present an example of a long‐term association between populations of two mammalian species, eastern chipmunks ( Tamias striatus ) and white‐footed mice ( Peromyscus leucopus ), which are commonly associated with deciduous forest habitats. The distribution of mitochondrial DNA variation in T. striatus and P. leucopus from previously glaciated regions of the eastern United States support the hypothesis that, in at least part of their range, genetic lineages of the two species have expanded from similar population sources since the Last Glacial Maximum. In addition, the spatial concordance of genetic lineages of T. striatus and P. leucopus with the oak‐savannah forest formations of Wisconsin and Illinois, suggest that populations associated with this community colonized the area in association with a set of arboreal species that comprise their deciduous forest habitat.

Application of Diversity Indices to Appraise Plant Availability in the Traditional Medicinal Markets of Johannesburg, South Africa - Vivienne L. Williams; Edward T. F. Witkowski; Kevin Balkwill (Biodiversity and Conservation, 2005)

Sequence evolution and sex-specific expression patterns of the C class floral identity gene, SpAGAMOUS, in dioecious Spinacia oleracea L - D. Noah. Sather; Amber York; Kevin J. Pobursky; Edward M. Golenberg (Planta, 2005)

Osteoblast Elastic Modulus Measured by Atomic Force Microscopy Is Substrate Dependent - Erica Takai; Kevin D. Costa; Aisha Shaheen; Clark T. Hung; X. Edward Guo (Annals of Biomedical Engineering, 2005)

Multivariate statistical and other approaches for the separation of cereal from wild Poaceae pollen using a large Holocene dataset - John C. Tweddle; Kevin J. Edwards; Nick R. J. Fieller (Vegetation History and Archaeobotany, 2005)

Elm bark beetle in Holocene peat deposits and the northwest European elm decline - Sarah H. E. Clark; Kevin J. Edwards (Journal of Quaternary Science, 2004)
The elm decline of 5000 14 C yr ago has been the most widely discussed phenomenon in post‐glacial vegetation history. This pan‐European reduction of elm populations, echoed in the decimation of elmwoods in Europe during the twentieth century, has attracted a series of interrelated hypotheses involving climate change, human activity, disease and soil deterioration. The elm bark beetle ( Scolytus scolytus L.) is an essential component of disease explanations. We present evidence for the presence of the beetle over a prolonged period (ca. 7950–4910 yr BP [8800–5660 cal. yr BP]) from a lowland raised mire deposit in northeast Scotland, with its final appearance at this site, and the first and only appearance in another mire of a single scolytid find, around the time of the elm decline. The subfossil S. scolytus finds are not only the first from Scotland, but they also represent the most comprehensive sequence of finds anywhere. Copyright © 2004 John Wiley & Sons, Ltd.

Hybridization Between Canada Lynx and Bobcats: Genetic Results and Management Implications - Michael K. Schwartz; Kristine L. Pilgrim; Kevin S. McKelvey; Edward L. Lindquist; James J. Claar; Steve Loch; Leonard F. Ruggiero (Conservation Genetics, 2004)

Multiproxy Devensian Late‐glacial and Holocene environmental records at an Atlantic coastal site in Shetland - Graeme Whittington; Paul Buckland; Kevin. J. Edwards; Malcolm Greenwood; Adrian M. Hall; Marie Robinson (Journal of Quaternary Science, 2003)
Marine erosion at Clettnadal, West Burra island off the west coast of Shetland, caused the drainage of a small water body at Clettnadal, exposing deposits of Late Devensian and Holocene age. Pollen, diatom and invertebrate analyses have provided variable records of environmental change during stratigraphical event GI‐1. Event GS‐1 is revealed by the non‐pollen evidence, especially by Coleoptera, by sediment stratigraphy, and by radiocarbon dating. In contrast, the pollen evidence indicates that an arctic tundra flora, in which dwarf shrubs were prominent, persisted throughout the Late‐glacial. The Holocene brought colonisation by tree birch, but by ca. 9000 14 C yr BP the taxon had almost disappeared. This contrasts strongly with other Holocene pollen records for Shetland where both Betula and Corylus avellana ‐type survived longer—at some sites, for example, until ca. 2900 yr BP. The extreme westerly and exposed coastal situation of Clettnadal appears to be responsible both for a muted Late‐glacial response in the pollen record of terrestrial vegetation and for the early replacement of woodland by a maritime grassland. The results provoke questions concerning biological stability at times of marked climatic change. Copyright © 2003 John Wiley & Sons, Ltd.

Incidence of Stress in Benthic Communities along the U.S. Atlantic and Gulf of Mexico Coasts within Different Ranges of Sediment Contamination from Chemical Mixtures - Jeffrey L. Hyland; W. Leonard Balthis; Virginia D. Engle; Edward R. Long; John F. Paul; J. Kevin Summers; Robert F. Van Dolah (Environmental Monitoring and Assessment, 2003)

Social grouping and maternal behaviour in feral horses (Equus caballus): the influence of males on maternal protectiveness - Elissa Z. Cameron; Wayne L. Linklater; Kevin J. Stafford; Edward O. Minot (Behavioral Ecology and Sociobiology, 2003)

A Multivariate Analysis of Biophysical Parameters of Tallgrass Prairie Among Land Management Practices and Years - Jerry A. Griffith; Kevin P. Price; Edward A. Martinko (Environmental Monitoring and Assessment, 2001)

Tissue distribution and functional expression of the human voltage-gated sodium channel β3 subunit - Edward B. Stevens; Peter J. Cox; Bhaval S. Shah; Alistair K. Dixon; Peter J. Richardson; Robert D. Pinnock; Kevin Lee (Pflügers Archiv - European Journal of Physiology, 2001)

Surface pollen‐vegetation relationships on the Atlantic seaboard: South Uist, Scotland - Barbara A. Brayshay; David D. Gilbertson; Martin Kent*; Kevin J. Edwards; Peter Wathern; Ruth E. Weaver (Journal of Biogeography, 2000)
Studies of modern pollen rain from remote islands have raised a number of interesting issues concerning the spatial precision of present‐day pollen spectra in relation to their parent plant community types. This paper examines the relationships and degree of correlation between a sequence of contemporary vegetation types, environments and their associated surface pollen spectra from a transect across the island of South Uist in the Outer Hebrides of Scotland. Paired data on both contemporary vegetation and associated surface pollen assemblages have been collected and analysed using methods of numerical classification and ordination. In general terms, the modern pollen rain on South Uist reflects the major changes in vegetation pattern and the major community types fairly closely. The major boundary between the alkaline machair sand dune communities and the various acidic upland vegetation types is particularly clear. However, both variability in the vegetation and the effects of the strong prevailing westerly and south‐westerly winds tend to blur the boundaries of the various communities within each of these larger categories. On average 86.6% of the palynomorphs come from in‐community quadrat sources, while only 1.3% are from off‐island sources. The limited present‐day tree distribution on the transect is discussed in the context of the more widespread distribution of arboreal pollen. Overall, there is a strong numerical correspondence between vegetation, pollen and environmental variables. The various problems inherent in examining surface pollen spectra are reviewed.

Palynology and people: observations on the British record - Kevin J. Edwards (Journal of Quaternary Science, 1999)

Preface - Kevin J. Edwards; Jon P. Sadler (Journal of Quaternary Science, 1999)

Landscape scale soil pollen analysis - Graeme Whittington; Kevin J. Edwards (Journal of Quaternary Science, 1999)

Introduction: striving for an environment-human consensus - Kevin J. Edwards; Jon P. Sadler (Journal of Quaternary Science, 1999)

Landscape scale soil pollen analysis - Graeme Whittington; Kevin J. Edwards (Journal of Quaternary Science, 1999)

Devensian organic interstadial deposits and ice sheet extent in Buchan, Scotland - Graeme Whittington; Rodger E. Connell; G. Russell Coope; Kevin J. Edwards; Adrian M. Hall; Peter D. Hulme; Jack Jarvis (Journal of Quaternary Science, 1998)

Devensian organic interstadial deposits and ice sheet extent in Buchan, Scotland - Graeme Whittington; Rodger E. Connell; G. Russell Coope; Kevin J. Edwards; Adrian M. Hall; Peter D. Hulme; Jack Jarvis (Journal of Quaternary Science, 1998)

A 12 000-year record of environmental change in the Lomond Hills, Fife, Scotland: Vegetational and climatic variability - Kevin J. Edwards; Graeme Whittington (Vegetation History and Archaeobotany, 1997)

Dating prehistoric bog‐fires in northern England to calendar years by long‐distance cross‐matching of pine chronologies - Frank M. Chambers; Jonathan G. A. Lageard; Gretel Boswijk; Peter A. Thomas; Kevin J. Edwards; Jennifer Hillam (Journal of Quaternary Science, 1997)

Dating prehistoric bog-fires in northern England to calendar years by long-distance cross-matching of pine chronologies - Frank M. Chambers; Jonathan G. A. Lageard; Gretel Boswijk; Peter A. Thomas; Kevin J. Edwards; Jennifer Hillam (Journal of Quaternary Science, 1997)

Long-distance marker horizons from small-scale eruptions: British tephra deposits from the AD 1510 eruption of Hekla, Iceland - ANDREW J. DUGMORE; ANTHONY J. NEWTON; KEVIN J. EDWARDS; GUDRÚN LARSEN; JEFFREY J. BLACKFORD; GORDON T. COOK (Journal of Quaternary Science, 1996)

Stable oxygen isotope and pollen records from eastern Scotland and a consideration of Late‐glacial and early Holocene climate change for Europe - GRAEME WHITTINGTON; ANTHONY E. FALLICK; KEVIN J. EDWARDS (Journal of Quaternary Science, 1996)

Stable oxygen isotope and pollen records from eastern Scotland and a consideration of Late-glacial and early Holocene climate change for Europe - GRAEME WHITTINGTON; ANTHONY E. FALLICK; KEVIN J. EDWARDS (Journal of Quaternary Science, 1996)